System and method for composite solid battery cell having ion conductive polymer electrolyte

Optimized solid-state batteries with ionically conductive polymer electrolytes address safety and efficiency issues in lithium-ion batteries by minimizing porosity and tortuosity, enhancing energy density and reducing resistance.

JP2024178299AActive Publication Date: 2024-12-24A123 SYSTEMS LLC
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024162472
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2019-07-01
Filing Date
2024-09-19
Publication Date
2024-12-24
Estimated Expiration
2040-07-01

AI Technical Summary

Technical Problem

Conventional lithium-ion batteries pose safety concerns due to their flammability and inefficiencies in packing materials, leading to reduced energy density and increased internal resistance, especially in automotive applications.

Method used

The use of ionically conductive polymer electrolytes in solid-state batteries, optimized through careful design and manufacturing processes to minimize porosity and tortuosity, ensuring a dense structure with a percolative network for ionic and electronic conduction, and incorporating specific particle size distributions and relative proportions of electrode active materials, solid polymer electrolytes, and conductive additives.

Benefits of technology

This approach enhances energy density, reduces resistance, and improves safety by eliminating flammability risks, while maintaining high power characteristics and mechanical stability in solid-state batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024178299000001_ABST
    Figure 2024178299000001_ABST
Patent Text Reader

Abstract

To provide a system and a method for a slurry for coating an electrode structure to reduce a resistance against a Li ion transportation, and improve a mechanical stability against the conventional solid battery cell.SOLUTION: In one example, a method can include steps of: mixing a solid ion conductive polymer material in a first part of at least solvent to one or both of a high shear force or a low shear force, and scattering a suspension; mixing one or a plurality of additives in the suspension to one or both of the high shear force or the low shear force; and mixing a second part of the solvent with the suspension in one or both of the high shear force or the low shear force to form a slurry, and scattering them. Therefore, the slurry containing the solid ion conductive polymer material can be executed to the solid battery cell in a solid battery cell.SELECTED DRAWING: Figure 1A
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims priority to U.S. Provisional Patent Application No. 62 / 869,407, filed July 1, 2019, entitled "SYSTEMS AND METHODS FOR A COMPOSITE SOLID-STATE BATTERY CELL WITH AN IONICALLY CONDUCTIVE POLYMER ELECTROLYTE," the entire contents of which are incorporated herein by reference for all purposes.

[0002] The present description relates generally to systems and methods for solid-state battery cells that include ionically conducting polymer materials. [Background technology]

[0003] The energy density of a secondary battery is an important figure of merit because it describes how many functions it can perform per unit mass or volume, calculated in terms of weight or volume, respectively. In the context of automotive applications, these measures are important because they indicate the distance a car can travel before needing to be recharged, relative to how much of the car's total mass or volume is dedicated to the modules responsible for the car's energy storage.

[0004] The energy density of a composite energy storage device is influenced by the theoretical gravimetric or volumetric capacity of the electrode active material and the amount of mass or volume units of electrode active material contained therein. Additionally, the packing efficiency of the materials comprising the energy storage device affects the energy density, whereby inefficiencies in the form of porosity or free volume are realized, which for a given capacity, manifest themselves in the form of increased capacity, or in the case of a fixed volume, resulting in decreased capacity. Porosity or free volume resulting from inefficient packing also has the effect of increased resistance, since voids within the electrode or electrolyte layer impede the path along which the charged species can travel. As the internal resistance increases, the power characteristics of the battery weaken, leading to a deterioration in performance when high charge or discharge rates are required. In the context of conventional lithium-ion batteries, a given degree of porosity can be acceptable and even of functional interest, since this space is permeated with a liquid electrolyte that facilitates the transport of lithium ions from the active material of one electrode to the active material of another electrode. This medium of ion transport offers a high level of mobility for lithium ions, but has the disadvantage of being highly flammable, resulting in safety concerns in the context of automotive or other transportation applications. Summary of the Invention [Problem to be solved by the invention]

[0005] It is desirable to eliminate the hazards associated with the flammability of the liquid electrolyte components of conventional Li-ion batteries, which has led to interest in replacing the liquid electrolyte with a solid-state electrolyte, thereby creating a need to eliminate any non-functional free space within the overall battery structure to optimize the performance characteristics described above. Solid-state electrolytes exist in many forms, including, by way of example, inorganic oxides and sulfides, as well as organic materials that include a continuum from gel polymer forms to solid polymer forms. [Means for solving the problem]

[0006] The inventors have recognized the above problems and have determined a solution that at least partially addresses them. To achieve a dense structure comprising a population of particulate materials, including but not limited to electrode active materials, solid polymer electrolytes, conducting additives, binders, and subpopulations of other organic and inorganic components of functional or passive nature, the inventors have recognized that the particle size distribution of the individual components and the relative percentage of the total solid volume can be carefully selected. These criteria facilitate the optimization of both the interparticle packing and the distribution of the particles relative to each other to preserve the functionality of the component materials. In addition to the pre-design of both the particulate populations alone and in combination with each other, it is paramount to take into account the process by which these materials are combined, as these affect both the size and proximal distribution of the composite morphology of the material. Aspects of the process by which the constituent materials are combined include substances introduced to facilitate mixing and formation, the order in which the component populations are combined, and the manner in which the components comprising the mixture from there are manipulated.

[0007] The design criteria and fabrication methods for each layer of the energy storage device may vary depending on the functionality required from the individual layers. As an example, an electrode comprising a mixture of powders of electrode active material, solid-state electrolyte and conductive additives, among others, may be constructed in some applications based on a population of electrode active particles among a population of smaller solid-state electrolyte and conductive additive particles. In such a configuration, particle size and distribution parameters may be selected to result in a layer with low porosity while also establishing a percolative network of solid-state electrolyte and conductive additives to support ionic and electronic conduction, respectively. To meet the functional requirements of the electrode layer, the energy content must be maximized by design by establishing a primary population of electrode active material interspersed with solid-state electrolyte and conductive additives in a continuous phase so that connectivity between the electrode active particles can be achieved. In this context, the volume occupied by the solid-state electrolyte and conductive additive particles may be sufficient to spread out the electrode active material particles to provide percolation paths without introducing unnecessary void space or occupying an excessive percentage of the solid volume to limit the realized electrochemical capacity of the layer. To meet such compositional and performance criteria, the population of electrode active material can be engineered to establish a predominant phase based on larger particle size, with a concomitant population of smaller particles occupying a portion of the free volume between the larger particles of electrode active material. The size distribution and relative percentages of the populations of other components can be manipulated relative to the situation in an interconnected network within the larger population of electrode active material particulates.

[0008] In contrast, the unique function of the separator dictates a different set of design criteria, whereby the resistance to lithium transport between the electrodes can be as low as possible while also acting as a mechanical barrier between the electrodes to prevent the occurrence of short circuits. The resistance to lithium transport between the electrodes can be minimized by formulating the electrolyte layer, which in this case can also function as a separator, from a material possessing high lithium conductivity values. The resistance to lithium migration can also be reduced by increasing the contact area between the electrode layer and the electrolyte and reducing the thickness of the electrolyte layer. In addition, the resistance of the electrolyte / separator layer can be reduced by configuring the particles that form the electrolyte layer in a way that reduces the tortuosity of the path that the lithium ions take from one electrode to another. In the absence of a requirement that the solid electrolyte must fit into the voids between the electrode active materials, as may be the case for the electrode layers, the particle size distribution for the optimized electrolyte layer design may be different from that selected for the electrode layers.

[0009] The method of differential tailoring of the size distribution and relative proportions of the component materials in the electrode and electrolyte layers can provide further opportunities for configuration optimization by inserting interfacial layers between these layers to promote the matching of the electrolyte and electrode layers in the most effective manner. As an example, tailoring the particle size distribution of the solid electrolyte in the interfacial layer between the electrode and electrolyte layers to match the surface morphology of the electrode layers can provide an optimal balance between the design criteria motivating the minimization of interfacial void space while also reducing the tortuosity of the percolation network that provides the connectivity between the boundaries of the electrode and electrolyte layers.

[0010] The properties for which the optimal design of each layer of a battery can lead to large differences between layers require a certain flexibility in the manufacturing process to realize each of these layers' maximum potential functionality in their combined form. Identifying a manufacturing method that meets this required flexibility, plus the large tuning of the parameters that define how each of these techniques is deployed, constitutes a large and non-intuitive challenge for practitioners tasked with producing solid-state batteries therefrom. Described herein are methods for producing solid-state batteries, their component layers, and the mixtures and materials from which they are derived.

[0011] As an example, a coated hybrid electrode is presented that provides at least some of the above-described solutions as detailed herein. In one example, a method for forming a slurry includes dividing a solvent into multiple portions and mixing a solid ion-conducting polymer material, for example, formed from polyphenylene sulfide or liquid crystal polymer, in a first portion of the solvent according to a step sequence to form a suspension, the solid ion-conducting polymer material having a molecular weight of 1×10 at room temperature. -5The solid ionically conductive polymeric material has an ionic conductivity of greater than 1000 S / cm and is in a glassy state at room temperature, the first portion of the solvent being approximately half of the total solvent content, mixing the first additive in the suspension, and subsequent to mixing the first additive in the suspension, mixing a second portion of the solvent with the suspension to form a slurry having a solids content of 25-80 wt.%, a d50 particle size distribution of less than 30 μm, a Hegman Gauge of less than 90 μm, and a viscosity of 500-2800 cps at 85 Hz, the mixing including mixing at high shear and mixing at low shear, the low shear being 10-55 rpm. In this manner, the slurry can be applied as a coating on an electrode structure, which can achieve reduced porosity from optimal particle distribution and improved percolation networks from selectively staged component introduction during the formation process, as compared to conventional solid state batteries. Additionally, the use of solid, ionically conductive polymer materials can further reduce resistance to Li-ion transport and improve mechanical stability within battery cells containing the coated electrode structures.

[0012] It should be understood that the foregoing Summary is provided to introduce a selection of concepts in a simplified form that are further described in the Detailed Description. It is not intended to identify key or essential features of the claimed subject matter, the scope of which is defined solely by the claims that follow the Detailed Description. Moreover, the claimed subject matter is not limited to implementations that solve any disadvantages discussed above or in any portion of the present disclosure. [Brief description of the drawings]

[0013] [Figure 1A] FIG. 2 shows a schematic structural diagram of a first exemplary configuration of a coated hybrid electrode. [Figure 1B] FIG. 2 shows a schematic structural diagram of a second exemplary configuration of a coated hybrid electrode. [Diagram 2]FIG. 1 illustrates a first exemplary method for forming a slurry for applying a coating to an electrode structure. [Diagram 3] FIG. 1 illustrates a second exemplary method for forming a slurry for applying a coating to an electrode structure. [Figure 4] FIG. 13 illustrates a third exemplary method for forming a slurry for applying a coating to an electrode structure. [Diagram 5] FIG. 1 illustrates an exemplary method for forming a coating on an electrode structure by a slurry-based coating process. [Figure 6] FIG. 13 is a plot showing bimodal particle size distribution in a slurry for a cathode material coating. [Figure 7] FIG. 13 is a plot showing particle size distribution in a slurry for a cathode material coating. [Figure 8] FIG. 13 is a plot showing viscosity versus shear rate in a slurry for a cathode material coating. [Figure 9] FIG. 1 illustrates a process flow diagram for forming a slurry for cathode material coating. [Figure 10] FIG. 1 shows a scanning electron microscope (SEM) image of particle size distribution in a slurry for cathode material coating. [Figure 11] FIG. 13 is a plot showing particle size distribution in a slurry for an anode material coating. [Figure 12] FIG. 13 is a plot showing viscosity versus shear rate in a slurry for an anode material coating. [Figure 13] FIG. 2 illustrates a first process flow diagram for forming a slurry for an anode material coating. [Figure 14] FIG. 2 illustrates a second process flow diagram for forming a slurry for an anode material coating. [Figure 15] FIG. 13 is a plot showing particle size distribution in a slurry for a separator coating. [Figure 16] FIG. 13 is a plot showing viscosity versus shear rate in a slurry for a separator coating. [Figure 17] FIG. 2 illustrates a first process flow diagram for forming a slurry for coating a separator. [Figure 18] FIG. 2 shows a second process flow diagram for forming a slurry for coating a separator. [Figure 19] FIG. 1 shows an SEM image of particle size distribution in a slurry for coating a separator. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The following description relates to systems and methods for solid-state battery cells that include ionically conductive polymer materials as electrolytes. In particular, the ionically conductive polymer materials can be solid ionically conductive powders, such as those in U.S. Patent Application Publication No. 2017 / 0018781, WO 2016 / 196873, and U.S. Patent Application Publication No. 2017 / 0005356, the contents of which are incorporated herein by reference, and solid ionically conductive powders, such as those manufactured by Ionic Materials Inc., Woburn, Massachusetts. The solid ionically conductive polymer materials can be synthesized from polymers, dopants, and ionic compounds. The base polymer can be semi-crystalline or fully crystalline. Common materials that can be used for the base polymer include liquid crystal polymers, and polyphenylene sulfide, also known as PPS, or semi-crystalline polymers with a crystallinity of greater than 30% or greater than 50%. Candidate liquid crystal polymer materials for the base polymer can include copolymers of p-hydroxybenzoic acid. Other candidate base polymers include poly(p-phenylene oxide), polyetheretherketone, polyphthalamide, polypyrrole, polyaniline, polysulfone, copolymers containing monomers of the listed materials, and mixtures thereof. The solid ionically conductive material can be thermoplastic. The solid ionically conductive material is conductive in the glassy state. The dopants are electron acceptors and can be DDQ, TCNE, chloranil, oxygen, ozone, and sulfur trioxide (SO3). Ion sources or "ionic compounds" can include salts commonly used in lithium ion batteries or other battery systems, such as LiTFSI (lithium bis-trifluoromethanesulfonimide), LiFSI (lithium bis(fluorosulfonyl)imide), lithium bis(oxalato)borate (LiB(C2O4)2, "LiBOB"), and other lithium ion compounds and combinations thereof. In particular, the solid ionically conductive polymer material can have a 1×10 ionic conductivity at room temperature. -5The ion-conducting polymer material can have an ionic conductivity of more than 1000 S / cm and a glassy state at room temperature. Thus, the ion-conducting polymer material can have high room temperature ionic conductivity and can be incorporated into various coatings of solid-state battery cells for electrochemical stability in a tunable and electrode-specific manner. Furthermore, the ion-conducting polymer material can remain in the form of a solid powder that can be insoluble in commonly used solvents. Thus, the ion-conducting polymer material can provide tuning / reducing interfacial impedance by varying particle size distribution, particle morphology, relative volume percentage, etc. Other solid polymer materials having similar functions and properties may be substituted within the scope of this disclosure.

[0015] As described in more detail and as used herein, a battery can include an electrochemical storage device capable of converting chemical energy into electrical energy. A secondary battery can include a battery that, once it reaches a discharged state, can be returned to a charged state by application of an external current or voltage according to a given set of specified criteria. A battery can include a plurality of cells configured in electrical combination with each other. Each cell can include at least two electrode layers and a separator layer. Each of the electrodes can include an electrode active material. The positive electrode active layer can be referred to as the cathode. The negative electrode active layer can be referred to as the anode.

[0016] Additionally, as described in more detail herein with respect to the process, the separator layer may be referred to as a separator, which may serve to prevent contact between the cathode and anode layers and to facilitate the transport of ionic species between the electrodes while preventing the transport of electronic species between the electrodes.

[0017] The separator layer is 1×10 -5These may include ionically conductive polymers, particularly solid ionically conductive polymeric materials, such as materials having an ionic conductivity of greater than S / cm and a crystallinity of at least about 30%, where the material is in a glassy state at room temperature and is formed from polyphenylene sulfide polymers or liquid crystal polymers. As used herein, "about" or "approximately" when referring to numerical values ​​may encompass deviations of 5% or less.

[0018] It should be appreciated that external electrical contact to the electrodes can be established using a current collector onto which the electrode layers are coated during the manufacturing process.

[0019] Additional layers can be introduced into the cell structure to improve the interface between the electrode layers and the separator or current collector layers. As explained, each layer of the cell's structure can be described by its components. For consistency, the following conventions have been adopted throughout this disclosure to describe the totality of composite layers: - Composite (whole) = component A + component B + component C + component D, where: ○ Component A: electrode active material, Component B: a solid polymer electrolyte material, or an ionically conductive solid-state polymer; Component C: free volume, and Component D: All other materials used in the formulation of the slurry and fabrication of the layers, including: D1: Binder material, D2: Electronic conductor or conductive additive; D3: Surfactant, D4: Solvent, D5: Ceramic ionic conductor (to reduce impedance), D6: Inorganic ceramics (for improved mechanical integrity), D7: Lithium salts, and · D8: Ion conductive additive.

[0020] 1A and 1B show various configurations of coated hybrid electrodes or battery cell subassemblies. FIGS. 6-8, 10-12, 15, 16, and 19 show plots illustrating various properties of composite slurries described herein. FIGS. 2-4 show exemplary methods for forming composite slurries for applying a coating to an electrode structure (e.g., a cathode material coating, an anode material coating, a cathode current collector, an anode current collector, or combinations thereof), where the electrode structure can then be incorporated into a battery cell. FIGS. 9, 13, 14, 15, and 18 show exemplary process flow diagrams for forming composite slurries. FIG. 5 shows an exemplary method for forming a coating on an electrode structure by a slurry-based coating process.

[0021] 1A, a coated hybrid electrode first configuration 100 or battery cell subassembly is shown. In turn, the coated hybrid electrode first configuration 100 can include an anode current collector 101, an anode material coating 102, an anode-separator interfacial coating 106, a separator coating 103, a cathode-separator interfacial coating 107, a cathode material coating 104, and a cathode current collector 105. Thus, the separator coating 103 can function as a battery separator.

[0022] One or more of the anode material coating 102 and the anode-separator interfacial coating 106 can include an anode active material including lithium. One or more of the cathode material coating 104 and the cathode-separator interfacial coating 107 can include a cathode active material including lithium. As described herein above, one or more of the anode material coating 102, the anode-separator interfacial coating 106, the separator coating 103, the cathode-separator interfacial coating 107, and the cathode material coating 104 can include an ionically conductive polymer material, or another solid polymer material.

[0023] In some examples, an adhesive interface can be defined between the separator coating 103 and the electrode structure. The adhesive interface can be a three-dimensional interface between the separator coating 103 and the electrode structure such that the separator coating 103 can conform to and penetrate the surface of the electrode structure. As a first example, the electrode structure can be an anode material coating 102 deposited on an anode current collector 101, with an optional anode-separator interfacial coating 106 deposited thereon. As a second example, the electrode structure can be a cathode material coating 104 deposited on a cathode current collector 105, with an optional cathode-separator interfacial coating 107 deposited thereon. In some examples, the adhesive interface can have a 180° peel strength of greater than 200 gf / in. Thus, the slurry-based coating methods described herein can result in greater adhesion than applying a single polymer electrolyte film, which in some examples can have a 180° peel strength of about 2.1 gf / in.

[0024] 1B, a second configuration of coated hybrid electrode 150 or battery cell subassembly is shown. In order, the second configuration of coated hybrid electrode 150 can include an anode current collector 101, an anode material coating 102, an anode-separator interfacial coating 106, a first separator coating 103a, a conventional battery separator 108, a second separator coating 103b, a cathode-separator interfacial coating 107, a cathode material coating 104, and a cathode current collector 105. In some instances, the conventional battery separator 108 may branch off a single separator coating 103.

[0025] 2 provides a first method 200 for forming a slurry including a solid, ionically conductive polymer material. In some examples, the slurry can be applied as a coating on an electrode structure by a slurry-based coating process. In some examples, the coating can be one of a cathode material coating, a cathode-separator interfacial coating, an anode-separator interfacial coating, and a separator coating, such as cathode material coating 104, anode material coating 102, cathode-separator interfacial coating 107, anode-separator interfacial coating 106, and separator coating 103, respectively, as described above with respect to FIGs. 1A and 1B.

[0026] In some examples, the first method 200 can use multiple mixers, which can be configured to perform 202-206, as described in more detail below. Each of the multiple mixers can operate at one or both high shear and low shear. Furthermore, in some examples, 202-206 can be performed sequentially, i.e., 202 to 204 to 206.

[0027] At 202, a solid ionically conductive polymeric material (e.g., component B) can be dispersed in at least a first portion of a solvent (e.g., component D4) to form a suspension. In some examples, at least the first portion of the solvent can include one or more additional components. Thus, the first portion of the solvent can include a solution.

[0028] At 204, one or more additives can be dispersed in the suspension. In some examples, the one or more additives can include an electrode active material (e.g., component A), a binder (e.g., component D1), a surfactant (e.g., component D3), and an inorganic ceramic (e.g., component D6).

[0029] At 206, a second portion of the solvent can be mixed with the suspension to form a slurry. The second portion of the solvent can be provided to reach a target solids content. Thus, in some examples, the slurry can have a solids content of 40-80 wt.%, a d10 particle size distribution of less than 1 μm, a d50 particle size distribution of less than 30 μm, a d90 particle size distribution of less than 60 μm, a d99 particle size distribution of less than 140 μm, a Hegman Gauge of less than 90 μm, and a viscosity of 500-2800 cps at 85 Hz. The first method 200 can then end.

[0030] 3, a second method 300 for forming a slurry including a solid, ionically conductive polymer material is shown. In some examples, the slurry can be applied as a coating on an electrode structure by a slurry-based coating process. In some examples, the coating can be one of a cathode material coating, a cathode-separator interfacial coating, and an anode-separator interfacial coating, such as cathode material coating 104, anode material coating 102, cathode-separator interfacial coating 107, and anode-separator interfacial coating 106, respectively, as described above with respect to FIG. 1A and FIG. 1B.

[0031] In some examples, the second method 300 can use multiple mixers, which can be configured to perform 302-310, as described in more detail below. Each of the multiple mixers can operate at one or both high shear and low shear. Furthermore, in some examples, 302-310 can be performed sequentially, i.e., 302 to 304 to 306 to 308 to 310.

[0032] At 302, a first portion of a binder (eg, component D1) can be dissolved in a first portion of a solvent (eg, component D4) to form a solution.

[0033] At 304, a conductive additive (eg, component D2) can be dispersed in a first portion of the solution to form a suspension.

[0034] At 306, the solid ionically conductive polymeric material (eg, component B) and a second portion of the solution can be dispersed in a suspension.

[0035] At 308, one or more additional additives and the remaining portion of the solution can be dispersed in the suspension. In some examples, the one or more additional additives can include an electrode active material (e.g., component A) and a second portion of the binder (e.g., component D1).

[0036] At 310, a second portion of the solvent can be mixed with the suspension to form a slurry. The second portion of the solvent can be provided to reach a target solids content. Thus, in some examples, the slurry can have a solids content of 40-80 wt.%, a d10 particle size distribution of less than 10 μm, a d50 particle size distribution of less than 30 μm, a d90 particle size distribution of less than 60 μm, a d99 particle size distribution of less than 140 μm, a Hegman Gauge of less than 90 μm, and a viscosity of 500-2800 cps at 85 Hz. The second method 300 can then end.

[0037] 4, a third method 400 for forming a slurry including a solid, ionically conductive polymer material is shown. In some examples, the slurry can be applied as a coating on an electrode structure by a slurry-based coating process. In some examples, the coating can be a separator coating, such as separator coating 103, as described above with reference to FIGS. 1A and 1B.

[0038] In some examples, the third method 400 can use multiple mixers, each of which can be configured to perform 402-412, as described in more detail below. Each of the multiple mixers can operate at one or both high shear and low shear. Further, in some examples, 402-412 can be performed sequentially, i.e., 402 to 404, 406, 408, 410, 412.

[0039] At 402, a solid ionically conductive polymeric material (e.g., component B) can be dispersed in at least a first portion of a solvent (e.g., component D4) to form a suspension. In some examples, at least the first portion of the solvent can include one or more additional components. Thus, the first portion of the solvent can include a solution.

[0040] At 404, the binder (e.g., component D1) and surfactant (e.g., component D3) can be dissolved in a second portion of the solvent. At 406, the inorganic ceramic (e.g., component D6) can be dissolved in a second portion of the solvent to form a solution. At 408, a portion of the solution can be dispersed in a suspension. At 410, the remaining portion of the solution can be dispersed in a suspension.

[0041] In some examples, at 412, a third portion of the solvent can be mixed with the suspension to form a slurry. The third portion of the solvent can be provided to reach a target solids content. Thus, in some examples, the slurry can have a solids content of 40-55 wt.%, a d10 particle size distribution of less than 1 μm, a d50 particle size distribution of less than 15 μm, a d90 particle size distribution of less than 60 μm, a d99 particle size distribution of less than 100 μm, a Hegman Gauge of less than 90 μm, and a viscosity of 500-2200 cps at 85 Hz. The third method 400 can then end.

[0042] FIG. 5 provides a further method 500 for forming a coating on an electrode structure by a slurry-based coating process. By this method, the electrode structure can be included in a battery cell. In some examples, the coating can be one of a cathode material coating, a cathode-separator interface coating, an anode-separator interface coating, and a separator coating, such as cathode material coating 104, anode material coating 102, cathode-separator interface coating 107, anode-separator interface coating 106, and separator coating 103, respectively, as described above with reference to FIG. 1A and FIG. 1B. In other examples, the coating can form one of a first tab protection strip and a second tab protection strip for an anode current collector and a cathode current collector, such as anode current collector 101 and cathode current collector 105, respectively, as described above with reference to FIG. 1A and FIG. 1B.

[0043] At 502, a slurry including a solid ionically conductive polymer material (e.g., component B) can be obtained. In some examples, the slurry can be a composite slurry as described hereinabove and can further include one or more of component A, component C, and component D. In some examples, the slurry can be in liquid form.

[0044] At 504, the slurry can be coated onto an electrode structure. In some examples, the electrode structure can include an anode current collector (e.g., 101), a cathode current collector (e.g., 105), a previously deposited anode material coating (e.g., 102), a previously deposited cathode material coating (e.g., 104), or a previously deposited separator coating (e.g., separator coating 103, anode-separator interface coating 106, cathode-separator interface coating 107, etc.). Numerous slurry-based coating processes can be utilized without departing from the scope of this disclosure, including, but not limited to, slot die coating, roll-to-roll coating (e.g., gravure coating, screen printing, flexography), doctor blade casting, tape casting, thermal spray (aerosol) coating, reverse comma coating, etc.

[0045] At 506, the coated electrode structure may be dried, and at 508, the coated electrode structure may be calendared. Within the scope of the present disclosure, each of the drying and calendaring may be optimized to obtain a desired coating process. The method 500 may then end.

[0046] The methods described herein can be applied in the form of cell coatings or layers, each of which is described in more detail below.

[0047] Cathode In one example, the cathode layer of the cell can include multiple materials, which can be characterized as powders insofar as they contain a large number of particles of similar composition and properties in an isolated population. These powders can be combined with other materials to form a slurry to facilitate the deposition of a continuous layer on a substrate that retains the functionality obtained from the composite. In the present case, this can be an assembly that includes a current collector or previously manufactured electrode, a separator, or a combination of these. Below, a description of the constituent materials, the means by which the materials can be combined to form a slurry, the properties of the slurry, and a method for casting the slurry are provided.

[0048] In one example, the composite, including the cathode and the slurry from which the cathode is derived, can be formed from a combination of multiple materials with both active and passive functionality. Some of these candidate materials can be developed on a sacrificial basis during the formation of the slurry and can later be removed after coating of the slurry.

[0049] The cathode composite in the form of a slurry or the like can be defined as follows. - Composite (whole) = Component A + Component B + Component C + Component D where component A corresponds to the cathode active material. where component B corresponds to the ion-conducting solid-state polymer. - where the component C corresponds to the free volume. - where component D corresponds to binders, additives and other functional and non-functional ingredients. Thereby, the cathode slurry may contain the following components: Ingredient A - one or a combination of active materials, such as one or more of the following active materials: lithium iron phosphate (LFP), spinel LNMO, LiCoPO4, LiNiPO4, LVP, LVPF, LiNi x Mn y Co zO2, or LiNi x Co y Al z O2 Component B - one or more solid ionically conductive polymeric materials as ionically conductive substances having a primary particle size of 0.01 to 20 μm; Component C Component D - component D1: a binder comprising at least one compound selected from the group comprising polyethers, polyesters, carboxymethylcellulose or polymers based on at least one monomer such as methyl methacrylate, acrylonitrile, styrene, butadiene, acrylic acid or vinylidene fluoride; - Component D2: Electronic conductors such as carbon black, Super P, vapor-grown carbon fiber, etc. - Component D3: one or more surfactants for slurry homogeneity, such as sulfates, sulfonates, phosphates, carboxylates, etc. - Component D4: one or more dispersion solvents such as acetone, isopropanol, methanol, toluene, n-methylpyrrolidone and water - Component D5: LiNbO3, LiTaO3, LiNb x Ta 1-x One or more inorganic additives for reduction of interfacial impedance including P2O5, B2O3, Al2O3, Ga2O3, Y2O3, La2O3, SiO2, ZrO2, TiO2, such as O3, BaTiO3, and compounds resulting from combinations thereof with possible addition of Li2O having a primary particle size of 0.01-10 microns. - Component D6: one or more additives for improving the mechanical integrity of the polymer electrolyte and providing a complementary function in the solid electrolyte layer, such as P2O5, B2O3, Al2O3, Ga2O3, Y2O3, La2O3, SiO2, ZrO2, TiO2, and compounds resulting from their combinations, including the possible addition of Li2O with a primary particle size of 0.01-10 μm.

[0050] Except for the solvent, the cathode slurry may contain the components listed above in the following ranges: - 0~15wt.% solid ion-conducting polymeric material - 80~95wt.% active material - Binder content of 0.1-10wt.% - 1~10wt.% electronic conductor - Surfactant content of 0-5wt.%

[0051] The composite volume of the cathode layer is Vol. total =%Vol. ComponentA +%Volume ComponentB +%Volume ComponentC +%Volume ComponentD It can be defined as: - The volume % of component A can be >35%, >45%, >55%, >60% or >65%. The volume % of component B can be <30%, <25%, <20%, <15% or <10%. The volume percent of component C can be <40%, <30%, <20% or <15%. The volume percent of component D can be <30%, <25%, <10% or <5%. The sum of the volume percentages of components C and D may be <40%, <30%, <20% or <15%.

[0052] The particle size of particles comprising components A and B in powder form can also be described by the following: - Average particle size A mean Of the volume percent containing component A that can be assigned a mean value of A, the percentage identified as A1 of the total population is 1,mean A mean The particles are characterized as having a particle size distribution that can be greater than 0.1. - Average particle size A mean Of the volume percent containing component A that can be assigned the mean value A, the percentage identified as A2 of the total population 2,mean A mean The particles are characterized as having a particle size distribution that may be less than - Average volume percent of component A 1,mean>A mean The particles belonging to the population having a particle size distribution described by A form 100%, <95%, <85% or <80%, and the remaining part of component A, identified by A2, is located in the interstices between the larger particles. 2,mean mean Belongs to the group. - Average particle size B mean Of the volume percent containing component B that can be assigned a mean value of B, the percentage identified as B1 of the entire population is 1,mean B mean The particles are characterized as having a particle size distribution that can be greater than 0.1. - Average particle size B mean Of the volume percent containing component B that can be assigned a mean value of B, the percentage identified as B2 of the entire population is 2,mean B mean The particles are characterized as having a particle size distribution that may be less than - Average volume percent of component B 1,mean >B mean The particles belonging to the population having a particle size distribution described by B1 form >80%, <85%, <90% or <95% of the B population, identified by B2, and the remaining part of the B population is located in the interstices between the larger particles. 2,mean mean Belongs to the group.

[0053] The relative proportions of components A and B that form the composite (whole) can be described as follows: - As the volume % of component A, which contains a certain percentage of the total solid volume, increases, the volume % of component B, which contains B2, will increase relative to the volume % of component B, which contains B1. In this way, the porosity can be kept low. - The ratio of volume % of component B with B1 to volume % of component B with B2 can be decreased as the ratio of component A1 to component A2 is decreased. In some instances, this method maintains a solid polymer electrolyte percolation network as the active material grows while maintaining the density of the SPE:AM by also reducing the particle size ratio of B1:B2. ​​The proportion of component A added to the composite (total) in the form of A1 can be 100%, <95%, <90%, <85% or <80%. The proportion of component B added to the composite (total) in the form of B1 can be 100%, <90%, <80%, <70%, <60% or <50%.

[0054] Prior to coating, the cathode slurry can in some examples be characterized by the following: - Viscosity of 1000 to 2600 cps at 85 Hz, measured by parallel plate rheometry - 45-75% solids content - Hegman gauge <80μm or <50μm - Particle size distribution such as: d10<10μm, d50<30μm, d90<60μm, d99<100μm

[0055] The calendering can be carried out in a low humidity environment at room temperature (20° C.) to 140° C. The thickness of the positive electrode after the calendering can be 100 to 400 μm.

[0056] Representative particle size distribution curves are shown in plot 600 of Figure 6 and plot 700 of Figure 7. The first peak represents the particle size due to component B, and the second peak at approximately 10 μm is due to component A.

[0057] A representative viscosity curve is shown in plot 800 of Figure 8, where viscosity is plotted against shear rate. In this example, the slurry exhibits shear thinning properties. Cathode Mix Slurry Process

[0058] Below, an exemplary procedure for forming the cathode slurry is provided.

[0059] Exemplary Procedure 1 for the Cathode Slurry Mixing Process: In this example, component D1 (binder) can be added in multiple stages as a solution. i. Mixing Speeds and Equipment In particular, dispersion of the ingredients can be achieved by a combination of a single shaft mixer with a sawtooth high shear disperser, a multi-shaft mixer with multiple high shear dispersers, and a low shear anchor mixer, or a low shear helical paddle. Throughout the mixing process, the mixing speed can be maintained as described below. Low shear shaft speed 10~55rpm High shear shaft from 0 to 1500 rpm ii. Dissolution of component D1 in component D4 First, component D1 can be dissolved in component D4 to form a 1-15 wt.% solution. Component D2 can be dispersed. iii. Variance of component D2 The solution of component D1 and component D2 in a ratio of 10-60% can be mixed for 30-90 minutes. After this step, the solid content is in the range of 5-30 wt.%. iv. Dispersion of component B Then, component B and another ratio of 5-40% of component D1 solution can be added to the above suspension and mixed for 30-90 minutes. Following this step, the solid content can be 10-50 wt.%. v. Dispersion of component A Half of component A can be added to the mixing vessel along with another proportion of component D1 solution of 10-70% and the solution can be mixed for another 45-120 minutes. After this step, the solid content can be 40-80 wt.%. The other half of component A and the remaining proportion of component D1 solution can be added to the mixing vessel and mixed for 120 minutes to 16 hours. vi. Target solids percentage In some instances, additional component D4 can be added at this point to target the final slurry properties described above. Following this process, the slurry properties can be: · d10<10μm, d50<30μm, d90<60μm, d99<100μm Hegman gauge <50μm Solid content of 40-80wt.% Viscosity of 2000-2600cps at 85Hz

[0060] An exemplary process flow diagram 900 of Procedure 1 is shown in FIG.

[0061] Exemplary Procedure 2 for the Cathode Slurry Mixing Process: As another example, a method involving the addition of binder as a powder in a single stage is provided. i. Mixing Speeds and Equipment In this example, dispersion of the ingredients can be accomplished with a combination of a single shaft mixer equipped with a sawtooth high shear disperser, a multi-shaft mixer equipped with multiple high shear dispersers, and a low shear anchor mixer, or a low shear helical paddle. In some embodiments, throughout the mixing process, the mixing speed can be maintained as described below. Low shear shaft speed 10~55rpm High shear shaft from 0 to 1500 rpm ii. Variance of component D2 Component D4, Component D1 and Component D2 can be mixed for 30-90 minutes. After this step, the solids content can be 5-30 wt.%. iii. Dispersion of component B Component B and further component D4 can be added to the above suspension and mixed for 30-90 minutes. Following this step, the slurry solids content can be 10-50 wt.%. iv. Dispersion of component A Half of component A can be added to the mixing vessel along with additional component D4. In this example, the solution can be mixed for an additional 45-120 minutes. After this step, the slurry solids content can be between 40-80 wt.%. The other half of component A, and additional component D4, can be added to the mixing vessel and mixed for 120 minutes to 16 hours. v. Target solids percentage In some instances, additional solvent may be added at this point to target the final slurry properties described above. After this step, the slurry properties may be: · d10<10μm, d50<30μm, d90<60μm, d99<100μm Hegman gauge <50μm Solid content of 40-80wt.% Viscosity of 1000-2000cps at 85Hz

[0062] Exemplary Procedure 3 for the Cathode Slurry Mixing Process: As another example, a procedure is provided that involves mixing using only a high shear disperser. i. Mixing Speeds and Equipment In this example, dispersion of the ingredients can be accomplished using a single shaft mixer equipped with a saw blade high speed disperser. Throughout the mixing process, the high shear shaft mixing speed can be kept between 0-1500 rpm. ii. Dissolution of component D1 in component D4 First, component D1 can be dissolved in component D4 to form a 1-15 wt.% solution. iii. Variance of component D2 Component D1 in D4 solution can be used, and component D2A from the options provided for component D2 above can be dispersed first. This can be mixed for 30-90 minutes. Then the second component, component D2B from the options provided for component D2 above can be dispersed for another 30-90 minutes. The solids content can be around 10%. iv. Dispersion of component B Component B can then be dispersed within the slurry for 30 to 90 minutes. After this step, the entirety of Component A can be added, where the slurry can undergo mixing for 2 to 12 hours. v. Target solids percentage Finally, ingredient D4 can be added to adjust the solids content of the slurry to 50-60%.

[0063] Table 1 provides an example of a slurry mixing process. Table 1: LiNi 0.8 Mn 0.1 Co 0.1 Example of cathode slurry mixing process using O2(NMC811) (cathode active material) [Table 1]

[0064] Alternatives to the mixing process for the distribution of solid electrolyte components are also contemplated. For example, the order in which the particulate populations of different materials can be added to the mixture is carefully selected to promote a distribution of component particles that preserves the functionality of the component materials and provides optimal density. Smaller particles have a tendency to intersperse among larger particles. For this to occur effectively, uniformity of distribution of the larger particles must first be established. Furthermore, to achieve high gravimetric capacity, the overall introduction of each of the component materials can be done in subsets, and the distribution of the larger particle populations relative to the smaller particles can be engineered.

[0065] Vol. total =%Vol. ComponentA +%Volume ComponentB +%Volume ComponentC +%Volume ComponentD Given the above definition of the composite volume of the cathode layer defined as: where component A corresponds to the cathode active material. where component B corresponds to the ion-conducting solid-state polymer. - where the component C corresponds to the free volume. - where component D corresponds to the volume resulting from the presence of binders, additives and other functional and non-functional ingredients. - Average particle size A mean Of the volume percent containing component A that can be assigned a mean value of A, the percentage identified as A1 of the total population is 1,mean A meanThe particles are characterized as having a particle size distribution that can be greater than 0.1. - Average particle size A mean Of the volume percent containing component A that can be assigned the mean value A, the percentage identified as A2 of the total population 2,mean A mean The particles are characterized as having a particle size distribution that may be less than - Average particle size B mean Of the volume percent containing component B that can be assigned a mean value of B, the percentage identified as B1 of the entire population is 1,mean B mean The particles are characterized as having a particle size distribution that can be greater than 0.1. - Average particle size B mean Of the volume percent containing component B that can be assigned a mean value of B, the percentage identified as B2 of the entire population is 2,mean B mean The particles are characterized as having a particle size distribution that may be less than

[0066] Considering the above design criteria, the following defines the order in which the components of the cathode layer can be combined to form a mixture of components A, B, C and D by a mixing process. Step 1. First, component A1 can be mixed with a portion of component B2. Step 2. Component A1 can be mixed with a portion of component D to provide a dispersed population of A1 particles decorated with B1 particles. Step 3. Independently or in combination with component A1, components B1 and A2 can be mixed together with the further addition of a portion of component D. Step 4. A portion of ingredient B2 can be added to the mixture. Step 5. The remaining portions of component B2 and component D can be added incrementally to the mixture until the mixture contains the entirety of components A1, A2, B1, B2 and D.

[0067] In addition to the above, the use of a discontinuous binder medium is considered part of component D. The use of a discontinuous binder medium provides the function of continuous conformal coverage without inhibiting the transport of charged species at the interfaces between the active material of the electrode and the ionically conductive particles dispersed throughout the layers of the battery, or between the polymeric solid state particles that form the electrolyte layer.

[0068] To deploy such a strategy, staged mixing is again utilized, whereby the active material of a given electrode can first be mixed with a solid electrolyte powder in a wet or dry slurry to establish a surface coating of the active material with the solid-state electrolyte. This ionically conductive powder-coated active material can then be mixed with a binder vehicle that is resistant to dissolution in the slurry solvent. Following mixing of the solid electrolyte-coated active material with the insoluble binder vehicle, additional soluble binder components can be added to tune the mechanical durability of the electrode without compromising the ion conductivity and functionality of the electroactive species.

[0069] An example of this process can be described as follows: Step 1. First, component A1 can be mixed with a portion of component B2. Step 2. Add the mixture of component A1 and component B2 to component D 1A (insoluble binder) and A1 particles modified with B2 particles, and D 1A (Insoluble binder) A dispersed mass with the particles can be provided. Step 3. Part of B1 and component D 1B (soluble binder) can be added to a mixture of component A1 and component B2 and component D1 (insoluble binder). Step 4. Independently or by mixing components A1, B2 and D 1A (insoluble) mixture, and components B1 and A2 are added to component D 1B A portion of the (soluble binder) may be further added and mixed together. Step 5. A portion of component B2 can be added to the mixture. Step 6. The mixture contains components A1, A2, B1, B2, and D. 1A and D. 1B until the whole of component B2 and component D can be included. 1B The remaining portion can be added to the mixture in stages.

[0070] To facilitate the intended distribution of the above components, the following parameters can be applied in using the method to guide optimization of component particle size distribution. The ratio of the average diameter of the electrode active material to the solid polymer electrolyte may be less than 7, less than 6, less than 5 or less than 4. - The most common particle size for cathode active material component A1 can be <20 microns, greater than 5 microns or 10 microns. - The most common particle sizes for cathode active material component A2 can be >0.5 microns, >1 micron, <15 microns, <5 microns or 1.5 microns. The minimum characteristic particle size of the cathode active material may be greater than 0.5, >1, >2 or >5 microns and the maximum characteristic particle size of the cathode may be <70, <50, <30, <20 or <15 microns. - The most common particle size of the solid polymer electrolyte component B1 can be <5 microns or >1.6 microns. - The most common particle sizes of the solid polymer electrolyte component B2 can be <1.5 microns, >0.35 microns or 0.7 microns. The minimum characteristic particle size of the solid polymer electrolyte may be <1 micron, <0.5 micron, <0.2 micron or <0.05 micron. The maximum characteristic particle size of the solid polymer electrolyte may be >10 microns, >20 microns or <50 microns. The particle size distribution of the subpopulations can be approximated using a log-normal distribution function that includes individual or multiple components. Component A and component B can be approximated using multiple components with log-normal distribution.

number

[0071] Cathode Slurry Coating Process In one example, the cathode slurry can be coated at a speed of 1-10 m / min using one of the coating methods described herein above (e.g., exemplary procedures 1, 2, or 3). Following coating, the electrode roll passes through a set of ovens where drying conditions can be set to achieve an evaporation rate range of 30-200 g / min. Values ​​in this range can be optimized for reduced migration or spatial gradients of component D1 (binder), net-like distribution of component B (solid ionically conductive polymeric material), optimized uniformity of coating weight across the width of the coating, and good coating adhesion (≥10 gf / in). The latter parameters can provide for subsequent stamping of the electrode without compromising the integrity of the coating due to delamination on the surface or along the edges of the stamped electrode.

[0072] Characterization of the 2D distribution of polymer electrolyte in the cathode The 2D distribution of component B is quantified from SEM-EDS images. In the SEM image 1000 as shown by Figure 10, the surface of the cathode coating is shown with component B highlighted in white and the background in black. -Using nearest neighbor distance (NND) analysis, the 2D distribution of the polymer electrolytes can be clustered with an average NND of 3-10 μm. - The maximum Feret distance, i.e. the longest distance between two points on the boundary of a component B particle, may be between 0.6 and 10 μm. - Particle area: 0.2~23μm 2 It can be said that: The circularity of the particles in the cathode, defined by:

number

[0073] anode Similar to the discussion of the cathode, the anode layer can also utilize the disclosed process. In one example, the anode layer of the cell can include multiple materials, which can be characterized as powders insofar as they contain a large number of particles of similar composition and properties in an isolated population. These powders can be combined with other materials to form a slurry to facilitate the deposition of a continuous layer on a substrate that retains the functionality obtained from the composite. In the present case, this can be an assembly including a current collector or previously manufactured electrode, a separator, or a combination thereof. Below, a description of the component materials, the means by which the materials can be combined to form a slurry, the properties of the slurry, and a method for casting the slurry are provided.

[0074] In this example, the anode, and the composite comprising the slurry from which the anode is derived, can be formed from a combination of multiple materials with both active and passive functionality. Some of these candidate materials can be developed on a sacrificial basis during the formation of the slurry, and later removed after casting of the slurry, during the steps required to finalize the fabrication of the layer.

[0075] The anode composite in the form of a slurry or the like can be defined as follows. - Composite (whole) = Component A + Component B + Component C + Component D where component A corresponds to the anode active material. where component B corresponds to the conductive solid-state polymer. - where the component C corresponds to the free volume. - where component D corresponds to binders, additives and other functional and non-functional ingredients. Thereby, the anode slurry may contain the following components: Ingredient A - one or a combination of the following active materials with a primary particle size between 0.01 and 20 μm, or a foil thickness of less than 50 μm: graphite, silicon, silicon oxide, lithium metal, lithium titanium oxide, etc. Component B - one or more solid ionically conductive polymeric materials as ionically conductive substances having a primary particle size of 0.01 to 20 μm; Component C Component D - component D1: a binder comprising at least one compound selected from the group comprising polyethers, polyesters, carboxymethylcellulose or polymers based on at least one monomer such as methyl methacrylate, acrylonitrile, styrene, butadiene, acrylic acid or vinylidene fluoride; - Component D2: Electronic conductors such as carbon black, Super P, vapor-grown carbon fiber, etc. - Component D3: one or more surfactants for slurry homogeneity, such as sulfates, sulfonates, phosphates, carboxylates, etc. - Component D4: one or more dispersion solvents such as acetone, isopropanol, methanol, toluene, n-methylpyrrolidone and water - Component D5: LiNbO3, LiTaO3, LiNb x Ta 1-xOne or more inorganic additives for reduction of interfacial impedance including P2O5, B2O3, Al2O3, Ga2O3, Y2O3, La2O3, SiO2, ZrO2, TiO2, such as O3, BaTiO3, and compounds resulting from combinations thereof with possible addition of Li2O having a primary particle size of 0.01-10 microns. - Component D6: one or more additives for improving the mechanical integrity of the polymer electrolyte and providing a complementary function in the solid electrolyte layer, such as P2O5, B2O3, Al2O3, Ga2O3, Y2O3, La2O3, SiO2, ZrO2, TiO2, and compounds resulting from their combinations, including the possible addition of Li2O with a primary particle size of 0.01-10 μm.

[0076] Except for the solvent, the anode slurry may contain the components listed above in the following ranges: - 0~10wt.% solid ion-conducting polymeric material - 85~95wt.% active material - Binder content of 0.1-10wt.% - 1~10wt.% electronic conductor - Surfactant content of 0-5wt.%

[0077] In this example, the composite volume of the anode layer is Vol. total =%Vol. ComponentA +%Volume ComponentB +%Volume ComponentC +%Volume ComponentD It can be defined as: - The volume % of component A can be >35%, >50%, >55%, >60% or >70%. Note that these values ​​include inclusion of porosity values ​​of 15-40 volume % as in the cathode example. The volume % of component B can be <35%, <30%, <25%, <20% or <15%. The volume percent of component C can be <40%, <30%, <20% or <15%. The volume percent of component D can be <30%, <25%, <10% or <5%. The sum of the volume percentages of components C and D may be <40%, <30%, <20% or <15%.

[0078] The particle size of particles comprising components A and B in powder form can also be described by the following: - Average particle size A mean Of the volume percent containing component A that can be assigned a mean value of A, the percentage identified as A1 of the total population is 1,mean A mean The particles are characterized as having a particle size distribution that can be greater than 0.1. - Average particle size A mean Of the volume percent containing component A that can be assigned the mean value A, the percentage identified as A2 of the total population 2,mean A mean The particles are characterized as having a particle size distribution that may be less than - Average volume percent of component A 1,mean >A mean The particles belonging to the population having a particle size distribution described by A form <100%, <95%, <85% or <80%, and the remainder of the component A, identified by A2, is located in the interstices between the larger particles. 2,mean mean Belongs to the group. - Average particle size B mean Of the volume percent containing component B that can be assigned a mean value of B, the percentage identified as B1 of the entire population is 1,mean B mean The particles are characterized as having a particle size distribution that can be greater than 0.1. - Average particle size B mean Of the volume percent containing component B that can be assigned a mean value of B, the percentage identified as B2 of the entire population is 2,mean B mean The particles are characterized as having a particle size distribution that may be less than - Average volume percent of component B 1,mean >B mean ​The particles belonging to the population having a particle size distribution described by B1 form >80%, <85%, <90% or <95% of the B population, identified by B2, and the remaining part of the B population is located in the interstices between the larger particles. 2,mean mean Belongs to the group.

[0079] The relative proportions of components A and B that form the composite (whole) can be described as follows: - As the volume % of component A, which comprises a certain percentage of the total solid volume, increases, the volume % of component B, which contains B2, will increase relative to the volume % of component B, which contains B1. - A decrease in the ratio of component A1 to component A2 will result in a decrease in the ratio of the volume % of component B containing B1 to the volume % of component B containing B2. The proportion of component A added to the composite (total) in the form of A1 can be 100%, <95%, <90%, <85%, <80% or <75%. The proportion of component B added to the composite (total) in the form of B1 may be 100%, <90%, <80%, <70%, <60%, <50%, 40%, <30%, <20% or <15%.

[0080] Prior to coating, the anode slurry can be characterized by the following: - Viscosity of 1100-2800cps at 85Hz - 40-65% solids content - Hegman gauge <80μm or <50μm - Particle size distribution such as: d10<10μm, d50<30μm, d90<60μm, d99<140μm

[0081] A representative particle size distribution curve is shown in plot 1100 of Figure 11. Table 2 provides the particle size distribution of the slurry for the anode material coating, while a representative viscosity curve is shown in plot 1200 of Figure 12, where viscosity is plotted against shear rate. ​Table 2: Particle size distribution of the slurry for anode material coating as shown by plot 1100. [Table 2]

[0082] It should be understood that the above method can be followed by calendering in a low humidity environment at room temperature (20° C.) to 60° C. The thickness of the negative electrode after calendering can be 100 to 400 μm.

[0083] Anode Slurry Mixing Process Exemplary Procedure 4 for Anode Slurry Mixing Process: Three-Step Addition of Component D1A Component D1A can be added in steps ii, iii and vi. i. Mixing Speeds and Equipment Dispersion of the ingredients can be accomplished with a combination of single shaft mixers with sawtooth high shear dispersers, multi-shaft mixers with multiple high shear dispersers, and low shear anchor stirrers, or low shear helical paddles. Throughout the mixing process, mixing speeds can be maintained as described below. Low shear shaft speed 10~55rpm High shear shaft from 0 to 1500 rpm ii. Dissolution of component D1 in component D4 First, components D1A and D1B can each be dissolved in component D4 to form two solutions at 0.5-3 wt.% and 25-60 wt.%, respectively. iii. Variance of component D2 A 5-30% ratio of component D1A solution and component D2 can be mixed for 30-90 minutes. After this step, the slurry can be characterized by a solids content of 1-25 wt.%. iv. Dispersion of component B Component B and another ratio of 30-70% of component D1A solution can be added to the above slurry and mixed for 30-90 minutes. After this step, the solid content can be 5-30wt.%. v. Dispersion of component A Adding half of component A to the mixing vessel can result in a solids content of 25-60 wt.% and the solution can be mixed for 45-120 minutes. Adding the other half of component A to the mixing vessel can result in a solids content of 40-70 wt.% and the solution can be mixed for 120 minutes to 16 hours. vi. Dispersion of component D1B Another proportion of 10-50% of component D1A can be added to the above slurry and mixed for 30-90 minutes to give a solids content of 40-70 wt.%. Component D1B solution can be added to the slurry and mixed for 30-90 minutes. After this step, the slurry can be characterized by a solids content of 40-65 wt.% and a viscosity of 1100-2800 cps. vii. Target solids percentage Any additional solvent can be added at this point to adjust the final slurry properties. The slurry can be mixed under vacuum for 30 to 120 minutes.

[0084] Exemplary Procedure 5 for Anode Slurry Mixing Process: Two-Stage Addition of Component D1A Component D1A can be added in steps ii and v. vi. Mixing Speeds and Equipment Dispersion of the ingredients can be accomplished with a combination of single shaft mixers with sawtooth high shear dispersers, multi-shaft mixers with multiple high shear dispersers, and low shear anchor stirrers, or low shear helical paddles. Throughout the mixing process, mixing speeds can be maintained as described below. Low shear shaft speed 10~55rpm High shear shaft from 0 to 1500 rpm vii. Dissolution of component D1 in component D4 First, components D1A and D1B can each be dissolved in component D4 to form two solutions at 0.5-3 wt.% and 25-60 wt.%, respectively. viii. Variance of component D2 Component D1A and component D2B in a ratio of 50-85% can be mixed for 30-90 minutes. After this step, the solid content can be 1-25 wt.%. ix. Dispersion of component B Component B can be added to the above slurry and mixed for 30-90 minutes. After this step, the solid content can be 5-30 wt.%. x. Dispersion of component A Half of component A can be added to the mixing vessel and the solution can be mixed for 45-120 minutes. After this step, the solids content is at 25-60 wt.%. The other half of component A and a 15-50% ratio of component D1A solution can be added to the mixing vessel and mixed for 120 minutes to 16 hours. After this step, the slurry properties can include a solids content of 40-70 wt.%. xi. Dispersion of component D1B The component D1B solution can be added to the slurry and mixed for 30 to 90 minutes. xii. Target solids percentage Any additional solvent can be added at this point to adjust the final slurry properties. The slurry can be mixed under vacuum for 30-120 minutes. The final slurry properties can be as follows: - d10<15μm, d50<30μm, d90<60μm, d99<100μm - Hegman gauge <80μm - Solid content of 40-65wt.% - Viscosity of 1100-2800cps at 85Hz

[0085] Exemplary Procedure 6 for the Anode Slurry Mixing Process: Single-Stage Addition of Primary Components A and B i. Mixing Speeds and Equipment Dispersion of the ingredients can be accomplished using a single shaft mixer equipped with a saw blade high speed disperser. Throughout the mixing process, the high shear shaft mixing speed can be kept between 500 and 1200 rpm. ii. Dissolution of component D1 in component D4 First, components D1A and D1B can each be dissolved in component D4 to form two solutions at 0.5-3 wt.% and 25-60 wt.%, respectively. iii. Variance of components D2, B and A Component D2 can be dispersed for 90-120 minutes in a certain ratio of Component D1A solution along with Component B and all of Component A. The solid content of the slurry in this step can be 40-60%. iv. Dispersion of component D1B Next, the slurry can be diluted with the remaining portion of the component D1A solution for 60-90 minutes. Finally, component D1B solution can be mixed into the slurry for 60-90 minutes. The final solids content can be 45-50%.

[0086] A process flow diagram 1300 of step 6 for the anode slurry mixing process is shown in FIG.

[0087] Exemplary Procedure 7 for the Anode Slurry Mixing Process: Single-Stage Addition of Primary Component A i. Mixing Speeds and Equipment Dispersion of the ingredients can be accomplished using a single shaft mixer equipped with a saw blade high speed disperser. Throughout the mixing process, the high shear shaft mixing speed can be kept between 500 and 1200 rpm. ii. Dissolution of component D1 in component D4 First, components D1A and D1B can each be dissolved in component D4 to form two solutions at 0.5-3 wt.% and 25-60 wt.%, respectively. iii. Variance of components D2 and D3 Ingredients D2 and D3 can be dispersed in the solution of ingredient D1A. The solid content in this step can be 1-15%. iv. Dispersion of component B Component B can be added and mixed for 30-90 minutes. The solids content in this step can be 5-30%. v. Dispersion of component A All of Component A can then be dispersed in the slurry for 90-120 minutes. The solids content in this step can be 40-70%. vi. Dispersion of component D1B Finally, component D1B solution can be mixed into the slurry for 30-60 minutes. The solids content at this step can be 45-65%.

[0088] An exemplary procedure 7 process flow diagram 1400 for the anode slurry mixing process is shown in FIG.

[0089] Exemplary Procedure 8 for Anode Slurry Mixing Process: Four-Step Addition of Component D1A i. Mixing Speeds and Equipment Dispersion of the ingredients can be accomplished with a combination of single shaft mixers with sawtooth high shear dispersers, multi-shaft mixers with multiple high shear dispersers, and low shear anchor stirrers, or low shear helical paddles. Throughout the mixing process, mixing speeds can be maintained as described below. Low shear shaft speed 10~55rpm High shear shaft from 0 to 1500 rpm ii. Dissolution of component D1 in component D4 First, components D1A and D1B can each be dissolved in component D4 to form two solutions at 0.5-3 wt.% and 25-60 wt.%, respectively. iii. Variance of components D2 and B The solution of component D1, component D2 and component B in a ratio of 55-90% can be mixed for 60-180 minutes. After this step, the solid content can be 5-20 wt.%. iv. Dispersion of component A Half of Component A can be added to the mixing vessel and the solution can be mixed for 60-240 minutes. After this step, the slurry characteristics include a solids content of 25-55 wt.%. The other half of Component A can be added to the slurry. At this point, a 10-45% proportion of Component D1A solution can be added. The slurry can be mixed for 120 minutes to 16 hours. After this step, the solids content can be 40-75 wt.%. v. Dispersion of the remaining part of component D1A At this point, a solution of component D1A can be added in a ratio of 10-45%. The slurry can be mixed for 30-60 minutes. After this step, the solids content can be 40-70 wt.%. vi. Dispersion of component D1B The remainder of the Component D1B solution and Component D1A solution can be added to the slurry. Some solvent can also be added at this step to adjust the slurry viscosity. The slurry can be mixed for 30 minutes to 16 hours. vii. Target solids percentage Any additional solvent can be added at this point to adjust the final slurry properties. The slurry can be mixed under vacuum for 30-120 minutes. The final slurry properties can be as follows: - d10<15μm, d50<30μm, d90<60μm, d99<100μm - Hegman gauge <80μm - Solid content of 40-65wt.% - Viscosity of 1100-2800cps at 85Hz

[0090] Table 3 provides an example of the anode slurry mixing process using graphite (anode active material). Table 3: Example of anode slurry mixing process using graphite (anode active material) [Table 3]

[0091] Alternative means to mixing for distribution of solid electrolyte components are also provided.

[0092] For example, the order in which the particulate populations of different materials can be added to the mixture can be carefully selected to promote a distribution of component particles that preserves the functionality of the component materials and provides optimal density. As explained above, smaller particles have a tendency to be interspersed among larger particles. For this to occur effectively, uniformity of distribution of the larger particles must first be established. Furthermore, the overall introduction of each of the component materials can be done in subsets, with the distribution of the larger particle populations relative to the smaller particles engineered to achieve the highest possible gravimetric capacity.

[0093] Vol. total =%Vol. ComponentA +%Volume ComponentB +%Volume ComponentC +%Volume ComponentD Given the above definition of the composite volume of the anode layer defined as: where component A corresponds to the anode active material. where component B corresponds to the ion-conducting solid-state polymer. - where the component C corresponds to the free volume. - where component D corresponds to the volume resulting from the presence of binders, additives and other functional and non-functional ingredients. - Average particle size A mean Of the volume percent containing component A that can be assigned a mean value of A, the percentage identified as A1 of the total population is 1,mean A mean The particles are characterized as having a particle size distribution that can be greater than 0.1. - Average particle size A meanOf the volume percent containing component A that can be assigned the mean value A, the percentage identified as A2 of the total population 2,mean A mean The particles are characterized as having a particle size distribution that may be less than - Average particle size B mean Of the volume percent containing component B that can be assigned a mean value of B, the percentage identified as B1 of the entire population is 1,mean B mean The particles are characterized as having a particle size distribution that can be greater than 0.1. - Average particle size B mean Of the volume percent containing component B that can be assigned a mean value of B, the percentage identified as B2 of the entire population is 2,mean B mean The particles are characterized as having a particle size distribution that may be less than

[0094] Considering the above design criteria, the following defines the order in which the components of the anode layer may be combined to form a mixture of components A, B, C and D by a mixing process. Step 1. First, component A1 can be mixed with a portion of component B2. Step 2. Component A1 can be mixed with a portion of component D to provide a dispersed population of A1 particles. Step 3. Independently or in combination with component A1, components B1 and A2 can be mixed together with the further addition of a portion of component D. Step 4. A portion of ingredient B2 can be added to the mixture. Step 5. The remaining portions of component B2 and component D can be added incrementally to the mixture until the mixture contains the entirety of components A1, A2, B1, B2 and D.

[0095] A further limitation of the above strategy involves the use of a discontinuous binder medium as part of component D. The use of a discontinuous binder medium provides the functionality of a continuous conformal coating without impeding the transport of charged species at the interface between the active material of the electrode and the ionically conductive particles dispersed throughout the layers of the battery, or between the polymer solid-state particles forming the electrolyte layer. To develop such a strategy, stepwise mixing is again utilized, whereby the active material of a given electrode can first be mixed with a solid electrolyte powder in a wet or dry slurry to establish a surface coating of the active material with the solid-state electrolyte. This ionically conductive powder-coated active material can then be mixed with a binder medium that is resistant to dissolution in the solvent of the slurry. Following the mixing of the solid electrolyte-coated active material with the insoluble binder medium, an additional soluble binder component can be added to adjust the mechanical resistance of the electrode without compromising the functionality of the ionically conductive and electroactive species.

[0096] An example of this process can be described as follows. Step 1. First, component A1 can be mixed with a portion of component B2. Step 2. Add the mixture of component A1 and component B2 to component D 1A (insoluble binder) and A1 particles modified with B2 particles, and D 1A (Insoluble binder) A dispersed mass with the particles can be provided. Step 3. Part of B1 and component D 1B (soluble binder) can be added to a mixture of component A1 and component B2 and component D1 (insoluble binder). Step 4. Independently or by mixing components A1, B2 and D 1A (insoluble) mixture, and components B1 and A2 are added to component D 1B A portion of the (soluble binder) may be further added and mixed together. Step 5. A portion of component B2 can be added to the mixture. Step 6. The mixture contains components A1, A2, B1, B2, and D. 1A and D.1B until the whole of component B2 and component D can be included. 1B The remaining portion can be added to the mixture in stages.

[0097] To facilitate the intended distribution of the above components, the following parameters can be used in the method to guide optimization of the component particle size distribution. The ratio of the average diameter of the electrode active material to the solid polymer electrolyte may be less than 7, less than 6, less than 5 or less than 4. - The most common particle size of the anode active material component A1 can be <30 microns, greater than 5 microns or 1 micron. - The most common particle sizes for the anode active material component A2 can be >0.5 microns, >1 micron, <5 microns or 1.5 microns. - The most common particle size of the solid polymer electrolyte component B1 can be <5 microns or >1.6 microns. - The most common particle sizes of the solid polymer electrolyte component B2 can be <1.5 microns, >0.35 microns or 0.7 microns. The minimum characteristic particle size of the solid polymer electrolyte may be <1 micron, <0.5 micron, <0.2 micron or <0.05 micron. The maximum characteristic particle size of the solid polymer electrolyte may be >10 microns, >20 microns or <50 microns. The minimum characteristic particle size of the anode active material may be greater than 0.5, >1, >2 or >5 microns and the maximum characteristic particle size of the anode may be <70, <60, <50, <40, <30, <20 or <15 microns. The particle size distribution of the subpopulations can be approximated using a log-normal distribution function that includes individual or multiple components. Component A and component B can be approximated using multiple components with log-normal distribution.

number

[0098] Anode Slurry Coating Process In one example, the anode slurry can be coated at a speed of 1-10 m / min using one of the coating methods described herein above (e.g., exemplary procedures 4, 5, 6, 7, or 8). Following coating, the electrode roll passes through a set of ovens where drying conditions can be set to achieve an evaporation rate range of 30-150 g / min. Values ​​in this range can be optimized for reduced migration or spatial gradients of component D1 (binder), net-like distribution of component B (solid ionically conductive polymeric material), optimized uniformity of coating weight across the width of the coating, and good coating adhesion (≥10 gf / in). The latter parameter can be important to perform subsequent stamping of the electrode without compromising the integrity of the coating due to delamination on the surface or along the edges of the stamped electrode.

[0099] Interfacial cathode-separator layer In another example, the interfacial cathode-separator layer of the cell can include multiple materials, which can be characterized as powders insofar as they contain a large number of particles of similar composition and properties in an isolated population. These powders can be combined with other materials to form a slurry to facilitate the deposition of a continuous layer on a substrate that retains the functionality obtained from the composite. In the present case, this can be an assembly that includes a current collector or previously manufactured electrode, a separator, or a combination thereof. Below, a description of the component materials, the means by which the materials can be combined to form a slurry, the properties of the slurry, and a method for casting the slurry are provided.

[0100] In one example, the interfacial cathode-separator layer and the composite comprising the slurry from which the interfacial cathode-separator layer is derived can be formed from a combination of multiple materials with both active and passive functionality. Some of these candidate materials can be developed on a sacrificial basis during the formation of the slurry and later removed after casting of the slurry during the steps required to finalize the fabrication of the layer.

[0101] The slurry used to apply the interfacial layer between the cathode layer and the separator layer must contain one or more solid, ionically conductive polymer materials as the primary ionically conductive medium, and a cathode active material as the primary energy storage medium. The primary particle size of the solid, ionically conductive polymer materials can be from 0.01 to 20 μm.

[0102] In one example, the interfacial cathode-separator composite in the form of a slurry or the like can be defined according to the following. - Composite (whole) = Component A + Component B + Component C + Component D where component A corresponds to the cathode active material. where component B corresponds to the ion-conducting solid-state polymer. - where the component C corresponds to the free volume. - where component D corresponds to the volume resulting from the presence of binders, additives and other functional and non-functional ingredients. Thereby, the interfacial cathode-separator slurry can include the following components: Ingredient A - one or a combination of active materials, such as one or more of the following active materials: lithium iron phosphate (LFP), spinel LNMO, LiCoPO4, LiNiPO4, LVP, LVPF, LiNi x Mn y Co z O2, or LiNi x Co y Al z O2 Component B - one or more solid ionically conductive polymeric materials as ionically conductive substances having a primary particle size of 0.01 to 20 μm; Component C Component D - component D1: a binder comprising at least one compound selected from the group comprising polyethers, polyesters, carboxymethylcellulose or polymers based on at least one monomer such as methyl methacrylate, acrylonitrile, styrene, butadiene, acrylic acid or vinylidene fluoride; - Component D2: Electronic conductors such as carbon black, Super P, vapor-grown carbon fiber, etc. - Component D3: one or more surfactants for slurry homogeneity, such as sulfates, sulfonates, phosphates, carboxylates, etc. - Component D4: one or more dispersion solvents such as acetone, isopropanol, methanol, toluene, n-methylpyrrolidone and water - Component D5: LiNbO3, LiTaO3, LiNb x Ta 1-xOne or more inorganic additives for reduction of interfacial impedance including P2O5, B2O3, Al2O3, Ga2O3, Y2O3, La2O3, SiO2, ZrO2, TiO2, such as O3, BaTiO3, and compounds resulting from combinations thereof with possible addition of Li2O having a primary particle size of 0.01-10 microns. - Component D6: one or more additives for improving the mechanical integrity of the solid electrolyte layer, including P2O5, B2O3, Al2O3, Ga2O3, Y2O3, La2O3, SiO2, ZrO2, TiO2, such as B2O3, Al2O3, γ-AlO(OH), Ga2O3, Y2O3, La2O3, and compounds resulting from their combinations, including the possible addition of Li2O with a primary particle size of 0.01-10 μm. - Component D7: LiClO4, LiAsF6, LiPF6, LiBF4, LiRFSO3, LiCH3SO3, LiN(RFSO2)2, LiC(RFSO2)3, LiTFSI (lithium trifluoromethanesulfonylimide), LiBOB (lithium bis(oxalato)borate), LiBETI (lithium bis(perfluoroethylsulfonyl)imide), etc. + One or more Li salts containing cations - component D8: one or more additives for reducing the interfacial impedance, for example urethane-containing molecules, such as urethane-functionalized PEG, urethane-functionalized perfluoropolyethers, and alkylurethanes; 1-methyl-3-pyrrolidinone; 1,3-dimethyl-3,4,5,6-tetrahydro-2(1H)-pyrimidinone; 1,5-dimethyl-2-pyrrolidinone; alkyl-substituted pyridinium-based ionic liquids, alkyl-substituted pyrrolidinium-based ionic liquids, and alkyl-substituted ammonium-based ionic liquids with counter anions, such as TFSI, PF6, BF4 anion; poly(ethylene glycols) substituted with terminal functional groups, such as carbonates (linear or cyclic), carbamates (linear or cyclic), or nitriles;poly(ethylene glycol) bis(carboxymethyl) ether;dioctyl sulfosuccinate sodium, lithium, or potassium salt;glycolic acid ethoxylate 4-tert-butylphenyl ether;glycolic acid ethoxylate lauryl ether;glycolic acid ethoxylate 4-nonylphenyl ether;glycolic acid ethoxylate oleyl ether;poly(ethylene glycol) 4-nonylphenyl 3-sulfopropyl ether sodium, lithium, or potassium salt;and sodium, lithium, or potassium dodecylbenzenesulfonate

[0103] In this example, excluding the solvent, the interfacial layer slurry between the cathode layer and the separator layer can include the components listed above in the following ranges: - 12~45wt.% solid ion-conducting polymeric material - 50~85wt.% active material - Binder content of 0.1-10wt.% - 1~10wt.% electronic conductor - Surfactant content of 0-5wt.%

[0104] In some instances, the composite volume of the cathode-separator interfacial layer is Vol. total =%Vol. ComponentA +%Volume ComponentB +%Volume ComponentC +%Volume ComponentDIt can be defined as: - The volume % of component A can be >15%, >30%, >45%, >50%, >55% or >60%. The volume % of component B can be <70%, <60%, <50%, <45%, <40%, <35%, <30% or <25%. The volume percent of component C can be <40%, <30%, <20 or <15%. The volume percent of component D can be <30%, <25%, <10% or <5%. The sum of the volume percentages of components C and D may be <40%, <30%, <20% or <15%.

[0105] The particle size of particles comprising components A and B in powder form can also be described by the following: - Average particle size A mean Of the volume percent containing component A that can be assigned a mean value of A, the percentage identified as A1 of the total population is 1,mean A mean The particles are characterized as having a particle size distribution that can be greater than 0.1. - Average particle size A mean Of the volume percent containing component A that can be assigned the mean value A, the percentage identified as A2 of the total population 2,mean A mean The particles are characterized as having a particle size distribution that may be less than - Average volume percent of component A 1,mean >A mean The remaining part of component A, identified by A2, comprises particles belonging to a population having a particle size distribution described by A 2,mean mean Belongs to the group. - Average particle size B mean Of the volume percent containing component B that can be assigned a mean value of B, the percentage identified as B1 of the entire population is 1,mean B mean The particles are characterized as having a particle size distribution that can be greater than 0.1.​ - Average particle size B mean Of the volume percent containing component B that can be assigned a mean value of B, the percentage identified as B2 of the entire population is 2,mean B mean The particles are characterized as having a particle size distribution that may be less than - Average volume percent of component B 1,mean >B mean The particles belonging to the population having a particle size distribution described by B form <100%, <95%, <85% or <80%, and the remaining part of component B is located in the interstices between the larger particles, identified by B2. 2,mean mean Belongs to the group.

[0106] For example, the relative proportions of components A and B that form the composite (whole) can be described as follows: The proportion of component A added to the composite (total) in the form of A1 can be 25%, <20%, <15%, <10%, <5%. The proportion of component B added to the composite (total) in the form of B1 can be >35%, >45%, >55%, >65%, >75%, >85%.

[0107] Prior to coating, the cathode-separator interfacial slurry can be characterized by the following: - Viscosity of 500 to 2600 cps at 85 Hz, measured by parallel plate rheometry - 40-75% solids content - Hegman gauges < 90μm or < 50μm - Particle size distribution such as: d10<10μm, d50<30μm, d90<60μm, d99<100μm

[0108] The thickness of the positive electrode including the interfacial cathode-separator interface layer after the calendering can be 105 to 450 μm. The calendering can be carried out at room temperature (20° C.) to 140° C. in a low humidity environment.

[0109] ​ Cathode-separator interface layer slurry mixing process Several exemplary processes are described below.

[0110] Exemplary Procedure 9 for the Cathode-Separator Interface Slurry Mixing Process: Addition of Component D1 (Binder) as a Solution in Multiple Stages i. Mixing Speeds and Equipment Dispersion of the ingredients can be accomplished with a combination of single shaft mixers with sawtooth high shear dispersers, multi-shaft mixers with multiple high shear dispersers, and low shear anchor stirrers, or low shear helical paddles. Throughout the mixing process, mixing speeds can be maintained as described below. Low shear shaft speed 10~55rpm High shear shaft from 0 to 1500 rpm ii. Dissolution of component D1 in component D4 First, component D1 can be dissolved in component D4 to form a 1-15 wt.% solution. iii. Variance of component D2 The solution of component D1 and component D2 in a ratio of 10-60% can be mixed for 30-90 minutes. After this step, the solid content is in the range of 5-30 wt.%. iv. Dispersion of component B Next, component B and another proportion of component D1 of 5-40% can be added to the above suspension and mixed for 30-90 minutes. Following this step, the solid content can be 10-50 wt.%. v. Dispersion of component A Half of component A can be added to the mixing vessel along with another proportion of component D1 solution of 10-70% and the solution can be mixed for another 45-120 minutes. After this step, the solid content can be 40-80 wt.%. The other half of component A and the remaining proportion of component D1 solution can be added to the mixing vessel and mixed for 120 minutes to 16 hours. vi. Target solids percentage At this point some additional component D4 can be added to target the final slurry properties as described in the options provided for component D4 above. After this step the slurry properties should be as follows: · d10<10μm, d50<30μm, d90<60μm, d99<100μm Hegman gauge <50μm Solid content of 40-80wt.% Viscosity of 2000-2600cps at 85Hz

[0111] A process flow diagram 900 of an exemplary procedure 9 is shown in FIG.

[0112] Exemplary Procedure 10 for Cathode-Separator Interface Slurry Mixing Process: Addition of Binder as Powder in a Single Stage i. Mixing Speeds and Equipment Dispersion of the ingredients can be accomplished with a combination of single shaft mixers with sawtooth high shear dispersers, multi-shaft mixers with multiple high shear dispersers, and low shear anchor stirrers, or low shear helical paddles. Throughout the mixing process, mixing speeds can be maintained as described below. Low shear shaft speed 10~55rpm High shear shaft from 0 to 1500 rpm ii. Variance of component D2 Component D4, Component D1 and Component D2 can be mixed for 30-90 minutes. After this step, the solids content can be 5-30 wt.%. iii. Dispersion of component B Component B and further component D4 can be added to the above suspension and mixed for 30-90 minutes. Following this step, the slurry solids content can be 10-50 wt.%. iv. Dispersion of component A Half of component A can be added to the mixing vessel along with additional component D4 and the solution can be mixed for an additional 45-120 minutes. After this step, the slurry solids content is at 40-80 wt.%. The other half of component A and additional component D4 can be added to the mixing vessel and mixed for 120 minutes to 16 hours. v. Target solids percentage Any additional solvent can be added at this point to target the final slurry properties as described herein above. After this step, the slurry properties can be: · d10<10μm, d50<30μm, d90<60μm, d99<100μm Hegman gauge <50μm Solid content of 40-80wt.% Viscosity of 1000-2000cps at 85Hz

[0113] Exemplary Procedure 11 for Cathode-Separator Interface Slurry Mixing Process: Mixing with High Shear Disperser Only i. Mixing Speeds and Equipment Dispersion of the ingredients can be accomplished using a single shaft mixer equipped with a saw blade high speed disperser. Throughout the mixing process, the high shear shaft mixing speed can be kept between 0-1500 rpm. ii. Dissolution of component D1 in component D4 First, component D1 can be dissolved in component D4 to form a 1-15 wt.% solution. iii. Variance of component D2 Component D1 in D4 solution can be used, and component D2A from the options provided for component D2 above can be dispersed first. This can be mixed for 30-90 minutes. Then the second component, component D2B from the options provided for component D2 above can be dispersed for another 30-90 minutes. The solids content can be around 10%. iv. Dispersion of component B Component B can then be dispersed within the slurry for 30 to 90 minutes. After this step, the entirety of Component A can be added, where the slurry can undergo mixing for 2 to 12 hours. v. Target solids percentage Finally, ingredient D4 can be added to adjust the solids content of the slurry to 50-60%.

[0114] Alternative means to mixing for distribution of solid electrolyte components are also provided.

[0115] As explained above in other examples, the order in which the particulate populations of different materials can be added to the mixture must be carefully selected to promote a distribution of component particles that preserves the functionality of the component materials and provides optimal density. Smaller particles have a tendency to intersperse among the larger particles. For this to occur effectively, uniformity of distribution of the larger particles must first be established. Furthermore, the overall introduction of each of the component materials can be done in subsets, and the distribution of the larger particle populations relative to the smaller particles can be engineered to achieve the highest possible gravimetric capacity.

[0116] The composite volume of the cathode-separator layer is Vol. total =%Vol. ComponentA +%Volume ComponentB +%Volume ComponentC +%Volume ComponentD It can be defined as: where component A corresponds to the cathode active material. where component B corresponds to the ion-conducting solid-state polymer. - where the component C corresponds to the free volume. - where component D corresponds to the volume resulting from the presence of binders, additives and other functional and non-functional ingredients. - Average particle size A mean Of the volume percent containing component A that can be assigned a mean value of A, the percentage identified as A1 of the total population is 1,mean A meanThe particles are characterized as having a particle size distribution that can be greater than 0.1. - Average particle size A mean Of the volume percent containing component A that can be assigned the mean value A, the percentage identified as A2 of the total population 2,mean A mean The particles are characterized as having a particle size distribution that may be less than - Average particle size B mean Of the volume percent containing component B that can be assigned a mean value of B, the percentage identified as B1 of the entire population is 1,mean B mean The particles are characterized as having a particle size distribution that can be greater than 0.1. - Average particle size B mean Of the volume percent containing component B that can be assigned a mean value of B, the percentage identified as B2 of the entire population is 2,mean B mean The particles are characterized as having a particle size distribution that may be less than

[0117] Considering the above design criteria, the following defines the order in which the components of the cathode-separator layer may be combined to form a mixture of components A, B, C and D by a mixing process. Step 1. Components A2 and B1 can be combined in steps and mixed with a portion of component D to provide a dispersed population. Step 2. A portion of Component B2 is added to the mixture, and a portion of Component D can also be added. Step 3. The remaining portions of component B2 and component D can be added incrementally to the mixture until the mixture contains the entirety of components A2, B1, B2 and D.

[0118] Similarly, as explained above, the above strategy can use a discontinuous binder medium as part of component D. The use of a discontinuous binder medium provides the functionality of a continuous conformal coating without impeding the transport of charged species at the interface between the active material of the electrode and the ionically conductive particles dispersed throughout the layers of the battery, or between the polymeric solid-state particles forming the separator layer. To deploy such a strategy, stepwise mixing is again utilized, whereby the active material of a given electrode can first be mixed with a solid electrolyte powder in a wet or dry slurry to establish a surface coating of the active material with the solid-state electrolyte. This ionically conductive powder-coated active material can then be mixed with a binder medium that is resistant to dissolution in the solvent of the slurry. Following the mixing of the solid electrolyte-coated active material with the insoluble binder medium, an additional soluble binder component can be added to adjust the mechanical resistance of the electrode without compromising the functionality of the ionically conductive and electroactive species.

[0119] For example, one version of this process can be described as follows: Step 1. Components A2 and B1 can be combined in steps and mixed with a portion of component D to provide a dispersed population. Step 2. Add the mixture of components A2 and B1 to component D 1A (insoluble binder) and mixed with A2, B1 and D 1A A dispersed population of particles can be provided. Step 3. Add a portion of Component B2 to the mixture and Component D 1B A portion of the soluble binder may further be added. Step 4. Add components B2 and D until the mixture contains the entirety of components A2, B1, B2 and D. 1B The remaining portion of (the soluble binder) can be added stepwise to the mixture.

[0120] Similar to the above discussion, the following parameters may be applied to guide the optimization of component particle size distribution to facilitate the intended distribution of the above components. The ratio of the average diameter of the electrode active material to the solid polymer electrolyte may be less than 7, less than 6, less than 5 or less than 4. - The most common particle size for cathode active material component A1 can be <20 microns, greater than 5 microns or 10 microns. - The most common particle sizes for cathode active material component A2 can be >0.5 microns, >1 micron, <15 microns, <5 microns or 1.5 microns. The minimum characteristic particle size of the cathode active material may be greater than 0.5, >1, >2 or >5 microns and the maximum characteristic particle size of the cathode may be <70, <50, <30, <20 or <15 microns. - The most common particle size of the solid polymer electrolyte component B1 can be <5 microns or >1.6 microns. - The most common particle sizes of the solid polymer electrolyte component B2 can be <1.5 microns, >0.35 microns or 0.7 microns. The minimum characteristic particle size of the solid polymer electrolyte may be <1 micron, <0.5 micron, <0.2 micron or <0.05 micron. The maximum characteristic particle size of the solid polymer electrolyte may be >10 microns, >20 microns or <50 microns. The particle size distribution of the subpopulations can be approximated using a log-normal distribution function that includes individual or multiple components. Component A and component B can be approximated using multiple components with log-normal distribution.

number

[0121] Cathode-separator interface layer slurry coating process In one example, the cathode-separator interfacial layer can be coated, cast, deposited or placed on the positive electrode, the negative electrode or both electrodes to ensure high conformity between the separator layer and the electrodes. The coating process can be carried out according to the following configuration. - The same separator formulation coated on the anode and cathode - Two different separator formulations coated on the anode, allowing for optimized chemical and electrochemical stability between each electrode and the separator - Successive layers of different formulations coated on the anode and / or cathode, allowing for a gradient of separator composition that improves the chemical and electrochemical stability of the electrode

[0122] To ensure that the separator layer continuously covers the electrode it is covering, the width of the two covering layers can be the same, and the width of the separator layer can also be slightly larger than the covering width of the supporting electrode.

[0123] The cathode-separator interfacial layer slurry can be coated at a speed of 1-10 m / min using one of the coating methods described herein above (e.g., exemplary procedures 9, 10, or 11). Following coating, the electrode roll passes through a set of ovens where drying conditions can be set to achieve an evaporation rate range of 30-200 g / min. Values ​​in this range can be optimized for reduced migration or spatial gradients of component D1 (binder), net-like distribution of component B (solid ionically conductive polymeric material), optimized uniformity of coating weight across the width of the coating, and good coating adhesion (≧10 gf / in). The latter parameters can provide for subsequent stamping of the electrode without compromising the integrity of the coating due to delamination on the surface or along the edges of the stamped electrode.

[0124] Interfacial anode-separator layer In one example, the interfacial anode-separator layer of the cell can include multiple materials, which can be characterized as powders insofar as they contain a large number of particles of similar composition and properties in an isolated population. These powders can be combined with other materials to form a slurry to facilitate the deposition of a continuous layer on a substrate that retains the functionality obtained from the composite. In the present case, this can be an assembly that includes a current collector or previously manufactured electrode, a separator, or a combination thereof. Below, a description of the component materials, the means by which the materials can be combined to form a slurry, the properties of the slurry, and a method for casting the slurry are provided.

[0125] The interfacial anode-separator layer, and the composites that comprise the slurries from which the interfacial anode-separator layers are derived, can be formed from a combination of multiple materials with both active and passive functionality. Some of these candidate materials can be developed on a sacrificial basis during the formation of the slurry, and later removed after casting of the slurry, during the steps required to finalize the fabrication of the layer.

[0126] The slurry used to apply the interfacial layer between the anode layer and the separator layer must contain one or more solid, ionically conductive polymer materials as the primary ionically conductive medium, and an anode active material as the primary energy storage medium. The primary particle size of the solid, ionically conductive polymer materials can be from 0.01 to 20 μm.

[0127] The anode-separator composite in the form of a slurry or the like can be defined as follows. - Composite (whole) = Component A + Component B + Component C + Component D where component A corresponds to the anode active material. where component B corresponds to the ion-conducting solid-state polymer. - where the component C corresponds to the free volume. - where component D corresponds to the volume resulting from the presence of binders, additives and other functional and non-functional ingredients. Thereby, the interfacial anode-separator slurry may comprise the following components: Ingredient A - one or a combination of the following active materials with a primary particle size between 0.01 and 20 μm, or a foil thickness of less than 50 μm: graphite, silicon, silicon oxide, lithium metal, lithium titanium oxide, etc. Component B - one or more solid ionically conductive polymeric materials as ionically conductive substances having a primary particle size of 0.01 to 20 μm; Component C Component D - component D1: a binder comprising at least one compound selected from the group comprising polyethers, polyesters, carboxymethylcellulose or polymers based on at least one monomer such as methyl methacrylate, acrylonitrile, styrene, butadiene, acrylic acid or vinylidene fluoride; - Component D2: Electronic conductors such as carbon black, Super P, vapor-grown carbon fiber, etc. - Component D3: one or more surfactants for slurry homogeneity, such as sulfates, sulfonates, phosphates, carboxylates, etc. - Component D4: one or more dispersion solvents such as acetone, isopropanol, methanol, toluene, n-methylpyrrolidone and water - Component D5: LiNbO3, LiTaO3, LiNb x Ta 1-x One or more inorganic additives for reduction of interfacial impedance including P2O5, B2O3, Al2O3, Ga2O3, Y2O3, La2O3, SiO2, ZrO2, TiO2, such as O3, BaTiO3, and compounds resulting from combinations thereof with possible addition of Li2O having a primary particle size of 0.01-10 microns. - Component D6: one or more additives for improving the mechanical integrity of the solid electrolyte layer, including P2O5, B2O3, Al2O3, Ga2O3, Y2O3, La2O3, SiO2, ZrO2, TiO2, such as B2O3, Al2O3, γ-AlO(OH), Ga2O3, Y2O3, La2O3, and compounds resulting from their combinations, including the possible addition of Li2O with a primary particle size of 0.01-10 μm. - Component D7: LiClO4, LiAsF6, LiPF6, LiBF4, LiRFSO3, LiCH3SO3, LiN(RFSO2)2, LiC(RFSO2)3, LiTFSI (lithium trifluoromethanesulfonylimide), LiBOB (lithium bis(oxalato)borate), LiBETI (lithium bis(perfluoroethylsulfonyl)imide), etc. + One or more Li salts containing cations - component D8: one or more additives for reducing the interfacial impedance, for example urethane-containing molecules, such as urethane-functionalized PEG, urethane-functionalized perfluoropolyethers, and alkylurethanes; 1-methyl-3-pyrrolidinone; 1,3-dimethyl-3,4,5,6-tetrahydro-2(1H)-pyrimidinone; 1,5-dimethyl-2-pyrrolidinone; alkyl-substituted pyridinium-based ionic liquids, alkyl-substituted pyrrolidinium-based ionic liquids, and alkyl-substituted ammonium-based ionic liquids with counter anions, such as TFSI, PF6, BF4 anion; poly(ethylene glycols) substituted with terminal functional groups, such as carbonates (linear or cyclic), carbamates (linear or cyclic), or nitriles;poly(ethylene glycol) bis(carboxymethyl) ether;dioctyl sulfosuccinate sodium, lithium, or potassium salt;glycolic acid ethoxylate 4-tert-butylphenyl ether;glycolic acid ethoxylate lauryl ether;glycolic acid ethoxylate 4-nonylphenyl ether;glycolic acid ethoxylate oleyl ether;poly(ethylene glycol) 4-nonylphenyl 3-sulfopropyl ether sodium, lithium, or potassium salt;and sodium, lithium, or potassium dodecylbenzenesulfonate

[0128] Except for the solvent, the interfacial layer slurry between the anode layer and the separator layer will contain the components listed above in the following ranges: - 10~70wt.% solid ion-conducting polymeric material - 30~85wt.% active material - Binder content of 0.1-10wt.% - 1~10wt.% electronic conductor - Surfactant content of 0-5wt.% In this regard, the composite volume of the anode-separator interface layer is Vol. total =%Vol. ComponentA +%Volume ComponentB +%Volume ComponentC +%Volume ComponentD It can be defined as: - The volume % of component A can be >10%, >20%, >30%, >40%, >50% or >60%. The volume % of component B can be <85%, <75%, <65%, <55%, <45%, <35% or <30%. The volume percent of component C can be <40%, <30%, <20% or <15%. The volume percent of component D can be <30%, <25%, <10% or <5%. The sum of the volume percentages of components C and D may be <40%, <30%, <20% or <15%.

[0129] The particle size of particles comprising components A and B in powder form can also be described by the following: - Average particle size A mean Of the volume percent containing component A that can be assigned a mean value of A, the percentage identified as A1 of the total population is 1,mean A mean The particles are characterized as having a particle size distribution that can be greater than 0.1. - Average particle size A mean Of the volume percent containing component A that can be assigned the mean value A, the percentage identified as A2 of the total population 2,mean A mean The particles are characterized as having a particle size distribution that may be less than - Average volume percent of component A 1,mean >A mean The remaining part of component A, identified by A2, is made up of particles belonging to a population having a particle size distribution described by A 2,mean mean Belongs to the group. - Average particle size B mean Of the volume percent containing component B that can be assigned a mean value of B, the percentage identified as B1 of the entire population is 1,mean B mean The particles are characterized as having a particle size distribution that can be greater than 0.1. - Average particle size B mean ​Of the volume percent containing component B that can be assigned a mean value of B, the percentage identified as B2 of the entire population is 2,mean B mean The particles are characterized as having a particle size distribution that may be less than - Average volume percent of component B 1,mean >B mean The particles belonging to the population having a particle size distribution described by B form <100%, <95%, <85% or <80%, and the remaining part of component B is located in the interstices between the larger particles, identified by B2. 2,mean mean Belongs to the group.

[0130] The relative proportions of components A and B that form the composite (whole) can be described as follows: The proportion of component A added to the composite (total) in the form of A1 can be 25%, <20%, <15%, <10%, <5%. The proportion of component B added to the composite (total) in the form of B1 can be >35%, >45%, >55%, >65%, >75%, >85%.

[0131] Prior to coating, the anode-separator interfacial slurry can be characterized by the following: - Viscosity of 500 to 2600 cps at 85 Hz - 40-75% solids content - Hegman gauges < 90μm or < 50μm - Particle size distribution such as: d10<10μm, d50<30μm, d90<60μm, d99<100μm

[0132] In this example, the positive electrode thickness including the anode-separator interface layer after calendering can be 105 to 450 μm.

[0133] Anode-separator interface layer slurry mixing process Below, an exemplary procedure for forming the anode-separator interfacial slurry is provided. ​

[0134] Exemplary Procedure 12 for Anode-Separator Interfacial Slurry Mixing Process: Three-Stage Addition of Component D1A Component D1A can be added in steps ii, iii and vi. i. Mixing Speeds and Equipment Dispersion of the ingredients can be accomplished with a combination of single shaft mixers with sawtooth high shear dispersers, multi-shaft mixers with multiple high shear dispersers, and low shear anchor stirrers, or low shear helical paddles. Throughout the mixing process, mixing speeds can be maintained as described below. Low shear shaft speed 10~55rpm High shear shaft from 0 to 1500 rpm ii. Dissolution of component D1 in component D4 First, components D1A and D1B can each be dissolved in component D4 to form two solutions at 0.5-3 wt.% and 25-60 wt.%, respectively. iii. Variance of component D2 A 5-30% ratio of component D1A solution and component D2 can be mixed for 30-90 minutes. After this step, the slurry can be characterized by a solids content of 1-25 wt.%. iv. Dispersion of component B Component B and another ratio of 30-70% of component D1A solution can be added to the above slurry and mixed for 30-90 minutes. After this step, the solid content can be 5-30wt.%. v. Dispersion of component A Adding half of component A to the mixing vessel can result in a solids content of 25-60 wt.% and the solution can be mixed for 45-120 minutes. Adding the other half of component A to the mixing vessel can result in a solids content of 40-70 wt.% and the solution can be mixed for 120 minutes to 16 hours. vi. Dispersion of component D1B Another proportion of 10-50% of component D1A can be added to the above slurry and mixed for 30-90 minutes to give a solids content of 40-70 wt.%. Component D1B solution can be added to the slurry and mixed for 30-90 minutes. After this step, the slurry can be characterized by a solids content of 40-65 wt.% and a viscosity of 1100-2800 cps. vii. Target solids percentage Any additional solvent can be added at this point to adjust the final slurry properties. The slurry can be mixed under vacuum for 30 to 120 minutes.

[0135] Exemplary Procedure 13 for Anode-Separator Interfacial Slurry Mixing Process: Two-Stage Addition of Component D1A Component D1A can be added in steps ii and v. i. Mixing Speeds and Equipment Dispersion of the ingredients can be accomplished with a combination of single shaft mixers with sawtooth high shear dispersers, multi-shaft mixers with multiple high shear dispersers, and low shear anchor stirrers, or low shear helical paddles. Throughout the mixing process, mixing speeds can be maintained as described below. Low shear shaft speed 10~55rpm High shear shaft from 0 to 1500 rpm ii. Dissolution of component D1 in component D4 First, components D1A and D1B can each be dissolved in component D4 to form two solutions at 0.5-3 wt.% and 25-60 wt.%, respectively. iii. Variance of component D2 Component D1A and component D2B in a ratio of 50-85% can be mixed for 30-90 minutes. After this step, the solid content can be 1-25 wt.%. iv. Dispersion of component B Component B can be added to the above slurry and mixed for 30-90 minutes. After this step, the solid content can be 5-30 wt.%. v. Dispersion of component A Half of component A can be added to the mixing vessel and the solution can be mixed for 45-120 minutes. After this step, the solids content is at 25-60 wt.%. The other half of component A and a 15-50% ratio of component D1A solution can be added to the mixing vessel and mixed for 120 minutes to 16 hours. After this step, the slurry properties can include a solids content of 40-70 wt.%. vi. Dispersion of component D1B The component D1B solution can be added to the slurry and mixed for 30 to 90 minutes. viii. Target solids percentage Any additional solvent can be added at this point to adjust the final slurry properties. The slurry can be mixed under vacuum for 30-120 minutes. The final slurry properties can be as follows: - d10<15μm, d50<30μm, d90<60μm, d99<100μm - Hegman gauge <80μm - Solid content of 40-65wt.% - Viscosity of 1100-2800cps at 85Hz

[0136] Exemplary Procedure 14 for Anode-Separator Interfacial Slurry Mixing Process: Single Stage Addition of Primary Components A and B i. Mixing Speeds and Equipment Dispersion of the ingredients can be accomplished using a single shaft mixer equipped with a saw blade high speed disperser. Throughout the mixing process, the high shear shaft mixing speed can be kept between 500 and 1200 rpm. ii. Dissolution of component D1 in component D4 First, components D1A and D1B can each be dissolved in component D4 to form two solutions at 0.5-3 wt.% and 25-60 wt.%, respectively. iii. Variance of components D2, B and A Component D2 can be dispersed for 90-120 minutes in a certain ratio of Component D1A solution along with Component B and all of Component A. The solid content of the slurry in this step can be 40-60%. iv. Dispersion of component D1B Next, the slurry can be diluted with the remaining portion of the component D1A solution for 60-90 minutes. Finally, component D1B solution can be mixed into the slurry for 60-90 minutes. The final solids content can be 45-50%.

[0137] Exemplary Procedure 15 for Anode-Separator Interfacial Slurry Mixing Process: Single Stage Addition of Primary Component A i. Mixing Speeds and Equipment Dispersion of the ingredients can be accomplished using a single shaft mixer equipped with a saw blade high speed disperser. Throughout the mixing process, the high shear shaft mixing speed can be kept between 500 and 1200 rpm. ii. Dissolution of component D1 in component D4 First, components D1A and D1B can each be dissolved in component D4 to form two solutions at 0.5-3 wt.% and 25-60 wt.%, respectively. iii. Variance of components D2 and D3 Ingredients D2 and D3 can be dispersed in the solution of ingredient D1A. The solid content in this step can be 1-15%. iv. Dispersion of component B Component B can be added and mixed for 30-90 minutes. The solids content in this step can be 5-30%. v. Dispersion of component A All of Component A can then be dispersed in the slurry for 90-120 minutes. The solids content in this step can be 40-70%. V. Dispersion of component D1B Finally, component D1B solution can be mixed into the slurry for 30-60 minutes. The solids content at this step can be 45-65%.

[0138] Exemplary Procedure 16 for Anode-Separator Interfacial Slurry Mixing Process: Four-Stage Addition of Component D1A i. Mixing Speeds and Equipment Dispersion of the ingredients can be accomplished with a combination of single shaft mixers with sawtooth high shear dispersers, multi-shaft mixers with multiple high shear dispersers, and low shear anchor stirrers, or low shear helical paddles. Throughout the mixing process, mixing speeds can be maintained as described below. Low shear shaft speed 10~55rpm High shear shaft from 0 to 1500 rpm ii. Dissolution of component D1 in component D4 First, components D1A and D1B can each be dissolved in component D4 to form two solutions at 0.5-3 wt.% and 25-60 wt.%, respectively. iii. Variance of components D2 and B The solution of component D1, component D2 and component B in a ratio of 55-90% can be mixed for 60-180 minutes. After this step, the solid content can be 5-20 wt.%. iv. Dispersion of component A Half of Component A can be added to the mixing vessel and the solution can be mixed for 60-240 minutes. After this step, the slurry properties can include a solids content of 25-55 wt.%. The other half of Component A can be added to the slurry. At this point, a 10-45% ratio of Component D1A solution can be added. The slurry can be mixed for 120 minutes to 16 hours. After this step, the solids content can be 40-75 wt.%. v. Dispersion of the remaining part of component D1A At this point, a solution of component D1A can be added in a ratio of 10-45%. The slurry can be mixed for 30-60 minutes. After this step, the solids content can be 40-70 wt.%. vi. Dispersion of component D1B The remainder of the Component D1B solution and Component D1A solution can be added to the slurry. Some solvent can also be added at this step to adjust the slurry viscosity. The slurry can be mixed for 30 minutes to 16 hours. vii. Target solids percentage Any additional solvent can be added at this point to adjust the final slurry properties. The slurry can be mixed under vacuum for 30-120 minutes. The final slurry properties can be as follows: - d10<15μm, d50<30μm, d90<60μm, d99<100μm - Hegman gauge <80μm - Solid content of 40-65wt.% - Viscosity of 1100-2800cps at 85Hz

[0139] Similar to the discussion above regarding the other layers, alternative approaches to mixing for distribution of solid electrolyte components are also provided.

[0140] In particular, the order in which the particulate populations of different materials may be added to the mixture must be carefully selected to promote a distribution of component particles that preserves the functionality of the component materials and provides optimal density. Smaller particles have a tendency to intersperse among the larger particles. For this to occur effectively, uniformity of distribution of the larger particles must first be established. Furthermore, the overall introduction of each of the component materials can be done in subsets, with the distribution of the larger particle populations relative to the smaller particles engineered to achieve the highest possible gravimetric capacity.

[0141] The composite volume of the anode-separator layer is Vol. total =%Vol. ComponentA +%VolumeComponentB +%Volume ComponentC +%Volume ComponentD It can be defined as: where component A corresponds to the anode active material. where component B corresponds to the ion-conducting solid-state polymer. - where the component C corresponds to the free volume. - where component D corresponds to the volume resulting from the presence of binders, additives and other functional and non-functional ingredients. - Average particle size A mean Of the volume percent containing component A that can be assigned a mean value of A, the percentage identified as A1 of the total population is 1,mean A mean The particles are characterized as having a particle size distribution that can be greater than 0.1. - Average particle size A mean Of the volume percent containing component A that can be assigned the mean value A, the percentage identified as A2 of the total population 2,mean A mean The particles are characterized as having a particle size distribution that may be less than - Average particle size B mean Of the volume percent containing component B that can be assigned a mean value of B, the percentage identified as B1 of the entire population is 1,mean B mean The particles are characterized as having a particle size distribution that can be greater than 0.1. - Average particle size B mean Of the volume percent containing component B that can be assigned a mean value of B, the percentage identified as B2 of the entire population is 2,mean B mean The particles are characterized as having a particle size distribution that may be less than

[0142] Considering the above design criteria, the following defines the order in which the components of the anode separator layer may be combined to form a mixture of components A, B, C and D via a mixing process. Components A2 and B1 can be combined in steps and mixed with a portion of component D to give a dispersed population. - A portion of component B2 is added to the mixture and a portion of component D can also be added. - The remaining portions of component B2 and component D can be added stepwise to the mixture until the mixture contains the entirety of components A2, B1, B2 and D.

[0143] A further limitation of the above strategy involves the use of a discontinuous binder medium as part of component D. The use of a discontinuous binder medium provides the functionality of a continuous conformal coating without impeding the transport of charged species at the interface between the active material of the electrode and the ionically conductive particles dispersed throughout the layers of the battery, or between the polymeric solid-state particles forming the separator layer. To develop such a strategy, stepwise mixing is again utilized, whereby the active material of a given electrode can first be mixed with a solid electrolyte powder in a wet or dry slurry to establish a surface coating of the active material with the solid-state electrolyte. This ionically conductive powder-coated active material can then be mixed with a binder medium that is resistant to dissolution in the solvent of the slurry. Following the mixing of the solid electrolyte-coated active material with the insoluble binder medium, an additional soluble binder component can be added to adjust the mechanical resistance of the electrode without compromising the functionality of the ionically conductive and electroactive species.

[0144] One version of this process can be described as follows. Step 1. Components A2 and B1 can be combined in steps and mixed with a portion of component D to provide a dispersed population. Step 2. Add the mixture of components A2 and B1 to component D 1A (insoluble binder) and mixed with A2, B1 and D 1A A dispersed population of particles can be provided. Step 3. Add a portion of Component B2 to the mixture and Component D 1B A portion of the soluble binder may further be added. Step 4. Add components B2 and D until the mixture contains the entirety of components A2, B1, B2 and D.1B The remaining portion of (the soluble binder) can be added stepwise to the mixture.

[0145] To facilitate the intended distribution of the above components, the following criteria can be applied to guide optimization of the component particle size distribution. The ratio of the average diameter of the electrode active material to the solid polymer electrolyte may be less than 7, less than 6, less than 5 or less than 4. - The most common particle size of the anode active material component A1 can be <30 microns, greater than 5 microns or 1 micron. - The most common particle sizes for the anode active material component A2 can be >0.5 microns, >1 micron, <5 microns or 1.5 microns. - The most common particle size of the solid polymer electrolyte component B1 can be <5 microns or >1.6 microns. - The most common particle sizes of the solid polymer electrolyte component B2 can be <1.5 microns, >0.35 microns or 0.7 microns. The minimum characteristic particle size of the solid polymer electrolyte may be <1 micron, <0.5 micron, <0.2 micron or <0.05 micron. The maximum characteristic particle size of the solid polymer electrolyte may be >10 microns, >20 microns or <50 microns. The minimum characteristic particle size of the anode active material may be greater than 0.5, >1, >2 or >5 microns and the maximum characteristic particle size of the anode may be <70, <60, <50, <40, <30, <20 or <15 microns. The particle size distribution of the subpopulations can be approximated using a log-normal distribution function that includes individual or multiple components. Component A and component B can be approximated using multiple components with log-normal distribution.

number

[0146] Anode-separator interface layer slurry coating process In one example, the anode-separator interfacial layer can be coated, cast, deposited or placed on the positive electrode, the negative electrode or both electrodes to ensure high conformity between the separator layer and the electrodes. The coating process can be carried out according to the following configuration. - The same separator formulation coated on and on the anode - Two different separator formulations coated on the anode, allowing for optimized chemical and electrochemical stability between each electrode and the separator - Successive layers of different formulations coated on and / or on the anode, allowing for a gradient of separator composition that improves the chemical and electrochemical stability of the electrode

[0147] To ensure that the separator layer continuously covers the electrode it is covering, the width of the two covering layers can be the same, and the width of the separator layer can also be slightly larger than the covering width of the supporting electrode.

[0148] The anode-separator interfacial layer slurry can be coated at a speed of 1-10 m / min using one of the coating methods described herein above (e.g., exemplary procedures 12, 13, 14, 15, or 16). Following coating, the electrode roll passes through a set of four ovens where the temperature and fan ventilation can be set as follows: - Oven 1 at 40~100℃ and 300~900rpm - Oven 2 at 50~110℃ and 300~900rpm - Oven 3 at 60~120℃ and 300~900rpm - Oven 4 at 80~140℃ and 300~900rpm

[0149] Separator layer (cathode side) In one example, the separator layer of the cell can include multiple materials, which can be characterized as powders insofar as they contain a large number of particles of similar composition and properties in an isolated population. These powders can be combined with other materials to form a slurry to facilitate the deposition of a continuous layer on a substrate that retains the functionality obtained from the composite. In the present case, this can be an assembly that includes a current collector or previously manufactured electrode, a separator, or a combination thereof. Below, a description of the component materials, the means by which the materials can be combined to form a slurry, the properties of the slurry, and a method for casting the slurry are provided. The details presented below apply to the casting of the separator layer to the cathode layer.

[0150] In one example, the separator layer, and the composite that includes the slurry from which the separator layer is derived, can be formed from a combination of multiple materials with both active and passive functionality. Some of these candidate materials can be developed on a sacrificial basis during the formation of the slurry, and later removed after casting of the slurry during the steps required to finalize the fabrication of the layer.

[0151] The slurry used to apply the separator layer on the electrodes must contain one or more solid ionically conductive polymer materials as the primary ionically conductive medium. The primary particle size of the solid ionically conductive polymer materials may be from 0.01 to 20 μm.

[0152] The separator composite in the form of a slurry or the like can be defined as follows. - Composite (whole) = Component A + Component B + Component C + Component D where component A corresponds to the electrode active material (not present). where component B corresponds to the ion-conducting solid-state polymer. - where component B corresponds to the free volume. - where component D corresponds to binders, additives and other functional and non-functional ingredients. Thereby, the separator slurry may contain the following components: Ingredient A (Non-existent) Component B - one or more solid ionically conductive polymeric materials as ionically conductive substances having a primary particle size of 0.01 to 20 μm; Component C Component D - component D1: a binder comprising at least one compound selected from the group comprising polyethers, polyesters, carboxymethylcellulose or polymers based on at least one monomer such as methyl methacrylate, acrylonitrile, styrene, butadiene, acrylic acid or vinylidene fluoride; - Component D3: one or more surfactants for slurry homogeneity, such as sulfates, sulfonates, phosphates, carboxylates, etc. - Component D4: Dispersion solvents such as acetone, isopropanol, methanol, toluene, n-methylpyrrolidone and water - Component D5: LiNbO3, LiTaO3, LiNb x Ta 1-xOne or more inorganic additives for reduction of interfacial impedance including P2O5, B2O3, Al2O3, Ga2O3, Y2O3, La2O3, SiO2, ZrO2, TiO2, such as O3, BaTiO3, and compounds resulting from combinations thereof with possible addition of Li2O having a primary particle size of 0.01-10 microns. - Component D6: one or more additives for improving the mechanical integrity of the solid electrolyte layer, including P2O5, B2O3, Al2O3, Ga2O3, Y2O3, La2O3, SiO2, ZrO2, TiO2, such as B2O3, Al2O3, γ-AlO(OH), Ga2O3, Y2O3, La2O3, and compounds resulting from their combinations, including the possible addition of Li2O with a primary particle size of 0.01-10 μm. - Component D7: LiClO4, LiAsF6, LiPF6, LiBF4, LiRFSO3, LiCH3SO3, LiN(RFSO2)2, LiC(RFSO2)3, LiTFSI (lithium trifluoromethanesulfonylimide), LiBOB (lithium bis(oxalato)borate), LiBETI (lithium bis(perfluoroethylsulfonyl)imide), etc. + One or more Li salts containing cations - component D8: one or more additives for reducing the interfacial impedance, for example urethane-containing molecules, such as urethane-functionalized PEG, urethane-functionalized perfluoropolyethers, and alkylurethanes; 1-methyl-3-pyrrolidinone; 1,3-dimethyl-3,4,5,6-tetrahydro-2(1H)-pyrimidinone; 1,5-dimethyl-2-pyrrolidinone; alkyl-substituted pyridinium-based ionic liquids, alkyl-substituted pyrrolidinium-based ionic liquids, and alkyl-substituted ammonium-based ionic liquids with counter anions, such as TFSI, PF6, BF4 anion; poly(ethylene glycols) substituted with terminal functional groups, such as carbonates (linear or cyclic), carbamates (linear or cyclic), or nitriles;poly(ethylene glycol) bis(carboxymethyl) ether;dioctyl sulfosuccinate sodium, lithium, or potassium salt;glycolic acid ethoxylate 4-tert-butylphenyl ether;glycolic acid ethoxylate lauryl ether;glycolic acid ethoxylate 4-nonylphenyl ether;glycolic acid ethoxylate oleyl ether;poly(ethylene glycol) 4-nonylphenyl 3-sulfopropyl ether sodium, lithium, or potassium salt;and sodium, lithium, or potassium dodecylbenzenesulfonate

[0153] Except for the solvent, the separator layer slurry will contain the components listed above in the following ranges: - 1~98wt.% solid ion-conducting polymeric material - Binder content of 1-10 wt.% - Li salt content of 0~10wt.% - Additive content of 15~95wt.% - Surfactant content of 0-5wt.% In this regard, the composite volume of the separator layer is Vol. total =%Vol. ComponentA +%Volume ComponentB +%Volume ComponentC +%Volume ComponentD It can be defined as: where component A corresponds to the electrode active material (not present). where component B corresponds to the ion-conducting solid-state polymer. - where the component C corresponds to the free volume. - where component D corresponds to the volume resulting from the presence of binders, additives and other functional and non-functional ingredients. - The volume percentage of component A can be 0%. The volume % of component B can be >80%, >85%, >90%, >95 or >97%. The volume % of component C can be <20%, <15%, <10%, <5% or <3%. The volume percent of component D can be <20%, <15%, <10%, <5% or <3%. The sum of the volume percentages of components C and D may be <20%, <15%, <10%, <5% or <3%.

[0154] The particle size of particles comprising component B in powder form can also be described by the following: - Average particle size B mean Of the volume percent containing component B that can be assigned a mean value of B, the percentage identified as B1 of the entire population is 1,mean B mean The particles are characterized as having a particle size distribution that can be greater than 0.1. - Average particle size B mean Of the volume percent containing component B that can be assigned a mean value of B, the percentage identified as B2 of the entire population is 2,mean B mean The particles are characterized as having a particle size distribution that may be less than - Average volume percent of component B 1,mean >B mean The particles belonging to the population having a particle size distribution described by B form <100%, <95%, <85% or <80%, and the remaining part of component B is located in the interstices between the larger particles, identified by B2. 2,mean mean Belongs to the group.

[0155] ​Prior to coating, the separator layer slurry can be characterized by the following: - Viscosity of 500-2200cps at 85Hz - 40-55% solids content - Hegman gauges < 90μm or < 50μm - Particle size distribution such as: d10<1μm, d50<15μm, d90<60μm, d99<100μm

[0156] A representative particle size distribution curve is shown in plot 1500 of Figure 15. Additionally, a representative viscosity curve is shown in plot 1600 of Figure 16, where viscosity is plotted against shear rate.

[0157] The thickness of the separator layer after the calendering can be 5 to 50 μm. The calendering can be carried out at room temperature (20° C.) to 140° C. in a low humidity environment.

[0158] Separator Layer Slurry Mixing Process Below, an exemplary procedure for forming the separator slurry is provided.

[0159] Exemplary Procedure 17 for the Separator-Slurry Mixing Process: Two separate starting suspensions of component B in component D4 and components D3+D6 in component D4 are combined in two steps. i. Mixing Speeds and Equipment Dispersion of the ingredients can be accomplished with a combination of single shaft mixers with sawtooth high shear dispersers, multi-shaft mixers with multiple high shear dispersers, as well as low shear anchor mixers, low shear helical paddles, or ultra high shear rotor / stator mixers. Throughout the mixing process, mixing speeds can be maintained as described below. Low shear shaft speed 10~55rpm High shear shaft from 0 to 1500 rpm ii. Suspension 1: Dissolution of components D1 and D3 in component D4 First, component D1 can be dissolved in component D4 to form a 1-15 wt.% solution. After component D1 is dissolved, component D3 can be added to the solution and mixed for 30-90 minutes. iii. Suspension 1: Dispersion of component D6 Component D6 can then be added and mixed for 30-90 minutes. The suspension can be stabilized / homogenized using an ultra-high shear rotor / stator mixer. The suspension can be characterized by: - d10<1μm, d50<5μm, d90<10μm, d99<30μm - Hegman gauge <50μm - Solid content of 40-65wt.% *Alternatively, the above suspension can be prepared by adding component D6 first, then component D3, and finally component D1. The suspension properties will remain the same as those listed above. iv. Suspension 2: Dispersion of component B in component D4 In a separate mixing vessel, component B can be mixed with component D4 at a solids content of 70-95 wt.% for 30-180 minutes. After this step, an addition of component D4 can be added to the mixing vessel and mixed for 30-90 minutes. At this time, the slurry properties can be as follows: - d10<1μm, d50<2μm, d90<15μm, d99<30μm - Hegman gauge <50μm - Solid content of 30-60wt.% v. Dispersion of suspension 1 into suspension 2 in two steps Half of suspension 1 containing ingredients D6, D1 and D3 in D4 can be added to suspension 2 from step iv above and mixed for 30-120 minutes. After this step the solids content can be 30-60 wt.%. The other half of suspension 1 containing ingredients D6, D1 and D3 in D4 can be added to the slurry and mixed for 30 minutes to 16 hours. After this step the slurry properties are as follows: - d10<1μm, d50<2μm, d90<15μm, d99<30μm - Hegman gauge <70μm - Solid content of 30-60wt.% - Viscosity of 2000-4500cps at 85Hz vi. Target solids percentage Component D4 can then be added incrementally to adjust the slurry viscosity to the final target. Each addition can be followed by a mixing step of 30-60 minutes. The slurry can also be mixed under vacuum for 30-120 minutes before coating. A sieving step can be used to achieve the required particle size distribution.

[0160] A process flow diagram 1700 of an exemplary procedure 17 is shown in FIG.

[0161] Exemplary Procedure 18 for the Separator Slurry Mixing Process: Three-step Addition of a Single Suspension of Component D6 in D4 to Component B i. Mixing Speeds and Equipment Dispersion of the ingredients can be accomplished with a combination of single shaft mixers with sawtooth high shear dispersers, multi-shaft mixers with multiple high shear dispersers, as well as low shear anchor mixers, low shear helical paddles, or ultra high shear rotor / stator mixers. Throughout the mixing process, mixing speeds can be maintained as described below. Low shear shaft speed 10~55rpm High shear shaft from 0 to 1500 rpm ii. Suspension 1: Component D6 in Component D4 Component D6 may be suspended in component D4 at a concentration of 40-60 wt.%. The suspension may be characterized by the following particle size distribution: d10<1 μm, d50<2 μm, d90<15 μm, d99<30 μm. iii. Dispersion of component B in suspension 1 with a given ratio Adding component B and component D1 to one-third of the suspension from step ii can result in a solids content of 50-65%. The slurry can be mixed for 30-120 minutes. Another third of the suspension from step ii can be added to the slurry to reduce the solids content to 45-60%. The slurry can be mixed for 30-120 minutes. The final third of the suspension from step ii can be added and mixed for 30-16 hours. After this step, the Hegman gauge should be less than 100 μm and the solids content should be 40-55%. iv. Target solids percentage Some solvent can be added incrementally to adjust the slurry viscosity to the final target.

[0162] A process flow diagram 1800 of an exemplary procedure 18 is shown in FIG.

[0163] Exemplary Procedure 19 for the Separator Slurry Mixing Process: Two-Step Addition of a Single Suspension of Component D6 in D4 to Component B i. Mixing Speeds and Equipment Dispersion of the ingredients can be accomplished with a combination of single shaft mixers with sawtooth high shear dispersers, multi-shaft mixers with multiple high shear dispersers, as well as low shear anchor mixers, low shear helical paddles, or ultra high shear rotor / stator mixers. Throughout the mixing process, mixing speeds can be maintained as described below. i Low shear force shaft at 10~40rpm ii. High shear shaft from 0 to 3500 rpm ii. Suspension of component D6 in component D4 Half of component D6 can be suspended in component D4 at a concentration of 45-60 wt.% and mixed for 30-120 minutes. iii. Dispersion of component B Component B and component D1 can be added to the suspension along with component D4 to target a solids content of 50-70 wt.%. The slurry can be mixed for 30-120 minutes. iv. Variance of the remaining part of component D6 Add Component D6 and the remaining half of Component D4 to the mixing vessel to bring the solids content to 45-60 wt.%. The slurry can be mixed for 30-120 minutes. After this step the Hegman gauge should be less than 90 μm. Additional Component D4 can be added incrementally to adjust the slurry viscosity to the final target.

[0164] Exemplary Procedure 20 for the Separator-Slurry Mixing Process: Two separate starting suspensions of component B in component D4 and component D6 in component D4 are combined in three steps. i. Mixing Speeds and Equipment Dispersion of the ingredients can be accomplished with a combination of single shaft mixers with sawtooth high shear dispersers, multi-shaft mixers with multiple high shear dispersers, as well as low shear anchor mixers, low shear helical paddles, or ultra high shear rotor / stator mixers. Throughout the mixing process, mixing speeds can be maintained as described below. Low shear shaft speed 10~45rpm High shear shaft from 0 to 1300 rpm ii. Suspension 1: Suspension of component D6 in component D4 Component D6 may be initially suspended in a solvent at a concentration of 40-60 wt.%. The suspension may be characterized by the following particle size distribution: d10<1 μm, d50<2 μm, d90<15 μm, d99<30 μm. iii. Suspension 1: Dispersion of component D1 Component D1 can then be added to the suspension and mixed for 30 minutes to 16 hours. After mixing, the suspension has a Hegman Gauge of <80 μm and a solids content of 40 to 65 wt.%. iv. Suspension 2: Dispersion of component B In a separate mixing vessel, component B can be mixed with a portion of component D4 for 30 to 180 minutes at a solids content of 70 to 95 wt.%. After this step, an additional portion of component D4 can be added to the mixing vessel and mixed for 30 to 90 minutes to reach a solids content of 40 to 65 wt.%. v. Dispersion of suspension 1 into suspension 2 in three steps One third of suspension 1 containing ingredients D6 and D4 can be added to the slurry from step iv and mixed for 30-120 minutes. The solids content can be 40-65 wt.% and the Hegman Gauge can be <40 μm. The second third of suspension 2 can be added to the slurry and mixed for 30-120 minutes. The solids content can be 35-63 wt.% and the Hegman Gauge can be <40 μm. The final third of suspension 2 can be added to the slurry and mixed for 30 minutes to 16 hours. After this step the slurry properties are as follows: - Hegman gauge <40μm - Solid content of 30-60wt.% - Viscosity of 3500-4500cps at 85Hz vi. Target solids percentage Ingredient D4 can then be added incrementally to adjust the slurry viscosity to the final target. Each addition can be followed by a mixing step of 30-60 minutes. The slurry can also be mixed under vacuum for 30-120 minutes before coating.

[0165] Table 4 provides an example of the separator-slurry mixing process. Table 4: LiNi 0.8 Mn 0.1 Co 0.1 Example of separator-slurry mixing process using O2 (NMC811) (cathode active material) and graphite (anode active material) [Table 4]

[0166] The slurry particle size distribution was evaluated using a Malvern Mastersizer 3000 laser particle size analyzer. For the separator layer, the target dry thickness can be less than 30 microns. Therefore, it may be desirable to achieve a particle size distribution where the majority of particles are less than the target thickness. This was achieved by the exemplary procedure 17 shown in the table. Additionally, the best full cell performance, as shown by first cycle efficiency, is also achieved by the exemplary procedure 17 of separator-slurry mixing.

[0167] Alternative approaches to mixing for distribution of solid electrolyte components are again discussed.

[0168] For example, the order in which the particulate populations of different materials can be added to a mixture must be carefully selected to promote a distribution of component particles that preserves the functionality of the component materials and provides optimal density. Smaller particles have a tendency to intersperse among the larger particles. For this to occur effectively, uniformity of distribution of the larger particles must first be established. Furthermore, the overall introduction of each of the component materials can be done in subsets, with the distribution of the larger particle populations relative to the smaller particles engineered to achieve the highest possible gravimetric capacity.

[0169] Vol. total =%Vol. ComponentA +%Volume ComponentB +%Volume ComponentC Given the above definition of the composite volume of the separator layer defined as: where component A corresponds to the ion-conducting solid-state polymer. - where component B corresponds to the free volume. - where component C corresponds to the volume resulting from the presence of binders, additives and other functional and non-functional ingredients. - Average particle size A mean Of the volume percent containing component A that can be assigned a mean value of A, the percentage identified as A1 of the total population is 1,mean A meanThe particles are characterized as having a particle size distribution that can be greater than 0.1. - Average particle size A mean Of the volume percent containing component A that can be assigned the mean value A, the percentage identified as A2 of the total population 2,mean A mean The particles are characterized as having a particle size distribution that may be less than - Average volume percent of component A 1,mean >A mean The particles belonging to the population having a particle size distribution described by A form <100%, <95%, <85% or <80%, and the remainder of the component A, identified by A2, is located in the interstices between the larger particles. 2,mean mean Belongs to the group.

[0170] Considering the above design criteria, the following defines the order in which the components of the separator coated on the cathode layer can be combined to form a mixture of components A, B and C by a mixing process. - A portion of component A1 can be mixed with a portion of component C to provide a dispersed population of A1 particles. - A further portion of component A1 can be mixed with a portion of component A2 and component C to provide a dispersed population of A1 particles. - The remaining portions of component A2 and component C can be added stepwise to the mixture until the mixture contains the entirety of components A1, A2, B and C.

[0171] To facilitate the intended distribution of the above components, the following criteria can be applied to guide optimization of the component particle size distribution. The minimum characteristic particle size of the solid polymer electrolyte may be <1 micron, <0.5 micron or <0.2 micron. The maximum characteristic particle size of the solid polymer electrolyte may be >1.5 microns, <2.0 microns or <2.5 microns. ​The particle size distribution of the subpopulations can be approximated using a log-normal distribution function that includes individual or multiple components. Component A can be approximated using multiple components (A1 and A2) that have a log-normal distribution.

number

[0172] Separator layer coating process In one example, the separator can be coated, cast, deposited or placed on the positive electrode, the negative electrode or both electrodes to ensure high conformity between the separator layer and the electrodes. The coating process can be carried out according to the following configuration. i. The same separator formulation coated on the anode and cathode ii. Two different separator formulations coated onto the anode, allowing for optimized chemical and electrochemical stability between each electrode and the separator. iii. Successive layers of different formulations coated on the anode and / or cathode allowing for a gradient in separator composition that improves the chemical and electrochemical stability of the electrodes.

[0173] To ensure that the separator layer continuously covers the electrode it is covering, the width of the two covering layers can be the same, and the width of the separator layer can also be slightly larger than the covering width of the supporting electrode.

[0174] The separator layer slurry can be coated at a speed of 1-10 m / min using one of the coating methods described herein above (e.g., exemplary procedures 17, 18, 19, or 20). Following coating, the electrode roll passes through a set of ovens where drying conditions can be set to achieve an evaporation rate range of 5-70 g / min. Values ​​in this range can be optimized for reduced migration or spatial gradients of component D1 (binder), net-like distribution of component B (solid ionically conductive polymeric material), optimized uniformity of coating weight across the width of the coating, and good coating adhesion (≧10 gf / in). The latter parameter can be important for subsequent stamping of the electrode without compromising the integrity of the coating due to delamination on the surface or along the edges of the stamped electrode.

[0175] Characterization of the polymer electrolyte 2D distribution in the separator layer The 2D distribution of component B is quantified from SEM-EDS images. In the SEM image 1900 as shown by Figure 19, the surface of the separator coating is shown with component B highlighted in white and the background in black. -Using nearest neighbor distance (NND) analysis, the 2D distribution of the polymer electrolytes can be clustered with an average NND of 2-5 μm. The maximum Feret distance, i.e. the longest distance between two points on the boundary of a polymer electrolyte particle, can be between 1 and 30 μm. - Particle area: 0.5~180μm 2 It can be said that: The circularity of the particles in the separator defined by the following may be between 0.2 and 1.0:

number

[0176] Separator layer (anode side) In one example, the separator layer of the cell can include multiple materials, which can be characterized as powders insofar as they contain a large number of particles of similar composition and properties in an isolated population. These powders can be combined with other materials to form a slurry to facilitate the deposition of a continuous layer on a substrate that retains the functionality obtained from the composite. In the case of the present invention, this can be an assembly that includes a current collector or previously manufactured electrode, a separator, or a combination thereof. Below, a description of the component materials, the means by which the materials can be combined to form a slurry, the properties of the slurry, and a method for casting the slurry are provided. The details presented below apply to the casting of the separator layer to the anode layer.

[0177] In one example, the separator layer, and the composite that includes the slurry from which the separator layer is derived, can be formed from a combination of multiple materials with both active and passive functionality. Some of these candidate materials can be developed on a sacrificial basis during the formation of the slurry, and later removed after casting of the slurry during the steps required to finalize the fabrication of the layer.

[0178] The slurry used to apply the separator layer on the electrodes must contain one or more solid ionically conductive polymer materials as the primary ionically conductive medium. The primary particle size of the solid ionically conductive polymer materials may be from 0.01 to 20 μm.

[0179] The separator composite in the form of a slurry or the like can be defined as follows. - Composite (whole) = Component A + Component B + Component C + Component D where component A corresponds to the electrode active material (not present). where component B corresponds to the ion-conducting solid-state polymer. - where the component C corresponds to the free volume. - where component D corresponds to binders, additives and other functional and non-functional ingredients. Thereby, the separator slurry may contain the following components: Ingredient A (Non-existent) Component B - one or more solid ionically conductive polymeric materials as ionically conductive substances having a primary particle size of 0.01 to 20 μm; Component C Component D - component D1: a binder comprising at least one compound selected from the group comprising polyethers, polyesters, carboxymethylcellulose or polymers based on at least one monomer such as methyl methacrylate, acrylonitrile, styrene, butadiene, acrylic acid or vinylidene fluoride; - Component D3: one or more surfactants for slurry homogeneity, such as sulfates, sulfonates, phosphates, carboxylates, etc. - Component D4: Dispersion solvents such as acetone, isopropanol, methanol, toluene, n-methylpyrrolidone and water - Component D5: LiNbO3, LiTaO3, LiNb x Ta 1-x One or more inorganic additives for reduction of interfacial impedance including P2O5, B2O3, Al2O3, Ga2O3, Y2O3, La2O3, SiO2, ZrO2, TiO2, such as O3, BaTiO3, and compounds resulting from combinations thereof with possible addition of Li2O having a primary particle size of 0.01-10 microns. - Component D6: one or more additives for improving the mechanical integrity of the solid electrolyte layer, including P2O5, B2O3, Al2O3, Ga2O3, Y2O3, La2O3, SiO2, ZrO2, TiO2, such as B2O3, Al2O3, γ-AlO(OH), Ga2O3, Y2O3, La2O3, and compounds resulting from their combinations, including the possible addition of Li2O with a primary particle size of 0.01-10 μm. - Component D7: LiClO4, LiAsF6, LiPF6, LiBF4, LiRFSO3, LiCH3SO3, LiN(RFSO2)2, LiC(RFSO2)3, LiTFSI (lithium trifluoromethanesulfonylimide), LiBOB (lithium bis(oxalato)borate), LiBETI (lithium bis(perfluoroethylsulfonyl)imide), etc. + One or more Li salts containing cations - component D8: one or more additives for reducing the interfacial impedance, for example urethane-containing molecules, such as urethane-functionalized PEG, urethane-functionalized perfluoropolyethers, and alkylurethanes; 1-methyl-3-pyrrolidinone; 1,3-dimethyl-3,4,5,6-tetrahydro-2(1H)-pyrimidinone; 1,5-dimethyl-2-pyrrolidinone; alkyl-substituted pyridinium-based ionic liquids, alkyl-substituted pyrrolidinium-based ionic liquids, and alkyl-substituted ammonium-based ionic liquids with counter anions, such as TFSI, PF6, BF4 anion; poly(ethylene glycols) substituted with terminal functional groups, such as carbonates (linear or cyclic), carbamates (linear or cyclic), or nitriles;poly(ethylene glycol) bis(carboxymethyl) ether;dioctyl sulfosuccinate sodium, lithium, or potassium salt;glycolic acid ethoxylate 4-tert-butylphenyl ether;glycolic acid ethoxylate lauryl ether;glycolic acid ethoxylate 4-nonylphenyl ether;glycolic acid ethoxylate oleyl ether;poly(ethylene glycol) 4-nonylphenyl 3-sulfopropyl ether sodium, lithium, or potassium salt;and sodium, lithium, or potassium dodecylbenzenesulfonate

[0180] Except for the solvent, the separator layer slurry will contain the components listed above in the following ranges: i. 1-98 wt.% solid ion-conducting polymer material ii. Binder content of 1-10 wt.% iii. Li salt content of 0-10 wt.% iv. Additive content of 15-95wt.% v. Surfactant content of 0-5 wt.% In this regard, the composite volume of the separator layer is Vol. total =%Vol. ComponentA +%Volume ComponentB +%Volume ComponentC +%Volume ComponentD It can be defined as: where component A corresponds to the electrode active material (not present). where component B corresponds to the ion-conducting solid-state polymer. - where the component C corresponds to the free volume. - where component D corresponds to the volume resulting from the presence of binders, additives and other functional and non-functional ingredients. - The volume percentage of component A can be 0%. The volume percentage of component B can be >80%, >85%, >90%, >95% or >97%. The volume % of component C can be <20%, <15%, <10%, <5% or <3%. The volume percent of component D can be <20%, <15%, <10%, <5% or <3%. The sum of the volume percentages of components C and D may be <20%, <15%, <10%, <5% or <3%.

[0181] The particle size of particles comprising component B in powder form can also be described by the following: - Average particle size B mean Of the volume percent containing component B that can be assigned a mean value of B, the percentage identified as B1 of the entire population is 1,mean B mean The particles are characterized as having a particle size distribution that can be greater than 0.1. - Average particle size B mean Of the volume percent containing component B that can be assigned a mean value of B, the percentage identified as B2 of the entire population is 2,mean B mean The particles are characterized as having a particle size distribution that may be less than - Average volume percent of component B 1,mean >B mean The particles belonging to the population having a particle size distribution described by B form <100%, <95%, <85% or <80%, and the remaining part of component B is located in the interstices between the larger particles, identified by B2. 2,mean mean Belongs to the group.

[0182] Prior to coating, the separator layer slurry can be characterized by the following: i. Viscosity of 500 to 2200 cps at 85 Hz ii. Solids content between 40 and 55% iii. Hegman gauge < 90μm or < 50μm iv. Particle size distribution as follows: d10<1μm, d50<15μm, d90<60μm, d99<100μm

[0183] The thickness of the separator layer after the calendering can be 5 to 50 μm. The calendering can be carried out at room temperature (20° C.) to 140° C. in a low humidity environment.

[0184] Separator Layer Slurry Mixing Process Below, an exemplary procedure for forming the separator slurry is provided.

[0185] Exemplary Procedure 21 for the Separator-Slurry Mixing Process: Two separate starting suspensions of component B in component D4 and components D3+D6 in component D4 are combined in two steps. i. Mixing Speeds and Equipment Dispersion of the ingredients can be accomplished with a combination of single shaft mixers with sawtooth high shear dispersers, multi-shaft mixers with multiple high shear dispersers, as well as low shear anchor mixers, low shear helical paddles, or ultra high shear rotor / stator mixers. Throughout the mixing process, mixing speeds can be maintained as described below. Low shear shaft speed 10~55rpm​ High shear shaft from 0 to 1500 rpm ii. Suspension 1: Dissolution of components D1 and D3 in component D4 First, component D1 can be dissolved in component D4 to form a 1-15 wt.% solution. After component D1 is dissolved, component D3 can be added to the solution and mixed for 30-90 minutes. iii. Suspension 1: Dispersion of component D6 Component D6 can then be added and mixed for 30-90 minutes. The suspension can be stabilized / homogenized using an ultra-high shear rotor / stator mixer. The suspension can be characterized by: - d10<1μm, d50<5μm, d90<10μm, d99<30μm - Hegman gauge <50μm - Solid content of 40-65wt.% Alternatively, the above suspension can be prepared by adding component D6 first, then component D3, and finally component D1. The suspension properties will remain the same as those listed above. iv. Suspension 2: Dispersion of component B in component D4 In a separate mixing vessel, component B can be mixed with component D4 at a solids content of 70-95 wt.% for 30-180 minutes. After this step, an addition of component D4 can be added to the mixing vessel and mixed for 30-90 minutes. At this time, the slurry properties can be as follows: - d10<1μm, d50<2μm, d90<15μm, d99<30μm - Hegman gauge <50μm - Solid content of 30-60wt.% v. Dispersion of suspension 1 into suspension 2 in two steps Half of suspension 1 containing ingredients D6, D1 and D3 in D4 can be added to suspension 2 from step iv above and mixed for 30-120 minutes. After this step the solids content can be 30-60 wt.%. The other half of suspension 1 containing ingredients D6, D1 and D3 in D4 can be added to the slurry and mixed for 30 minutes to 16 hours. After this step the slurry properties are as follows: - d10<1μm, d50<2μm, d90<15μm, d99<30μm - Hegman gauge <70μm - Solid content of 30-60wt.% - Viscosity of 2000-4500cps at 85Hz vi. Target solids percentage Component D4 can then be added incrementally to adjust the slurry viscosity to the final target. Each addition can be followed by a mixing step of 30-60 minutes. The slurry can also be mixed under vacuum for 30-120 minutes before coating. A sieving step can be used to achieve the required particle size distribution.

[0186] A process flow diagram 1700 of an exemplary procedure 21 is shown in FIG.

[0187] Exemplary Procedure 22 for the Separator-Slurry Mixing Process: Three-Step Addition of a Single Suspension of Component D6 in D4 to Component B i. Mixing Speeds and Equipment Dispersion of the ingredients can be accomplished with a combination of single shaft mixers with sawtooth high shear dispersers, multi-shaft mixers with multiple high shear dispersers, as well as low shear anchor mixers, low shear helical paddles, or ultra high shear rotor / stator mixers. Throughout the mixing process, mixing speeds can be maintained as described below. Low shear shaft speed 10~55rpm High shear shaft from 0 to 1500 rpm ii. Suspension 1: Component D6 in Component D4 Component D6 may be suspended in component D4 at a concentration of 40-60 wt.%. The suspension may be characterized by the following particle size distribution: d10<1 μm, d50<2 μm, d90<15 μm, d99<30 μm. iii. Dispersion of component B in suspension 1 with a given ratio Adding component B and component D1 to one-third of the suspension from step ii can result in a solids content of 50-65%. The slurry can be mixed for 30-120 minutes. Another third of the suspension from step ii can be added to the slurry to reduce the solids content to 45-60%. The slurry can be mixed for 30-120 minutes. The final third of the suspension from step ii can be added and mixed for 30-16 hours. After this step, the Hegman gauge should be less than 100 μm and the solids content should be 40-55%. iv. Target solids percentage Some solvent can be added incrementally to adjust the slurry viscosity to the final target.

[0188] A process flow diagram 1800 of an exemplary procedure 22 is shown in FIG.

[0189] Exemplary Procedure 23 for the Separator-Slurry Mixing Process: Two-Step Addition of a Single Suspension of Component D6 in D4 to Component B i. Mixing Speeds and Equipment Dispersion of the ingredients can be accomplished with a combination of single shaft mixers with sawtooth high shear dispersers, multi-shaft mixers with multiple high shear dispersers, as well as low shear anchor mixers, low shear helical paddles, or ultra high shear rotor / stator mixers. Throughout the mixing process, mixing speeds can be maintained as described below. Low shear shaft speed 10~40rpm High shear shaft from 0 to 3500 rpm ii. Suspension of component D6 in component D4 Half of component D6 can be suspended in component D4 at a concentration of 45-60 wt.% and mixed for 30-120 minutes. iii. Dispersion of component B Component B and component D1 can be added to the suspension along with component D4 to target a solids content of 50-70 wt.%. The slurry can be mixed for 30-120 minutes. iv. Variance of the remaining part of component D6 The remaining half of Component D6 and Component D4 can be added to the mixing vessel to provide a solids content of 45-60 wt.%. The slurry can be mixed for 30-120 minutes. After this step, the Hegman gauge should be less than 90 μm. Additional Component D4 can be added incrementally to adjust the slurry viscosity to the final target.

[0190] Exemplary Procedure 24 for the Separator-Slurry Mixing Process: Two separate starting suspensions of component B in component D4 and component D6 in component D4 are combined in three steps. i. Mixing Speeds and Equipment Dispersion of the ingredients can be accomplished with a combination of single shaft mixers with sawtooth high shear dispersers, multi-shaft mixers with multiple high shear dispersers, as well as low shear anchor mixers, low shear helical paddles, or ultra high shear rotor / stator mixers. Throughout the mixing process, mixing speeds can be maintained as described below. Low shear shaft speed 10~45rpm High shear shaft from 0 to 1300 rpm ii. Suspension 1: Suspension of component D6 in component D4 Component D6 may be initially suspended in a solvent at a concentration of 40-60 wt.%. The suspension may be characterized by the following particle size distribution: d10<1 μm, d50<2 μm, d90<15 μm, d99<30 μm. iii. Suspension 1: Dispersion of component D1 Component D1 can then be added to the suspension and mixed for 30 minutes to 16 hours. After mixing, the suspension has a Hegman Gauge of <80 μm and a solids content of 40 to 65 wt.%. iv. Suspension 2: Dispersion of component B In a separate mixing vessel, component B can be mixed with a portion of component D4 for 30 to 180 minutes at a solids content of 70 to 95 wt.%. After this step, an additional portion of component D4 can be added to the mixing vessel and mixed for 30 to 90 minutes to reach a solids content of 40 to 65 wt.%. v. Dispersion of suspension 1 into suspension 2 in three steps One third of suspension 1 containing ingredients D6 and D4 can be added to the slurry from step iv and mixed for 30-120 minutes. The solids content can be 40-65 wt.% and the Hegman Gauge can be <40 μm. The second third of suspension 2 can be added to the slurry and mixed for 30-120 minutes. The solids content can be 35-63 wt.% and the Hegman Gauge can be <40 μm. The final third of suspension 2 can be added to the slurry and mixed for 30 minutes to 16 hours. After this step the slurry properties are as follows: - Hegman gauge <40μm - Solid content of 30-60wt.% - Viscosity of 3500-4500cps at 85Hz vi. Target solids percentage Ingredient D4 can then be added incrementally to adjust the slurry viscosity to the final target. Each addition can be followed by a mixing step of 30-60 minutes. The slurry can also be mixed under vacuum for 30-120 minutes before coating.

[0191] Table 5 provides an example of the separator-slurry mixing process. Table 5: LiNi 0.8 Mn 0.1 Co 0.1 Example of separator-slurry mixing process using O2 (NMC811) (cathode active material) and graphite (anode active material) [Table 5]

[0192] The slurry particle size distribution was evaluated using a Malvern Mastersizer 3000 laser particle size analyzer. For the separator layer, the target dry thickness can be less than 30 microns. Therefore, it may be desirable to achieve a particle size distribution where the majority of particles are less than the target thickness. This was achieved by the exemplary procedure 21 shown in the table. Additionally, the best full cell performance as indicated by first cycle efficiency is also achieved by the exemplary procedure 21 of separator-slurry mixing.

[0193] Alternative approaches to mixing for the distribution of solid electrolyte components are also disclosed. For example, the order in which different material particulate populations may be added to the mixture must be carefully selected to promote distribution of component particles that preserves the functionality of the component materials and provides optimal density. Smaller particles have a tendency to intersperse among larger particles. For this to occur effectively, uniformity of distribution of larger particles must first be established. Furthermore, the overall introduction of each of the component materials can be done in subsets, and the distribution of the larger particle population relative to the smaller particles can be engineered to achieve the highest possible gravimetric capacity.

[0194] Vol. total =%Vol. ComponentA +%Volume ComponentB +%Volume ComponentC Given the above definition of the composite volume of the separator layer defined as: where component A corresponds to the ion-conducting solid-state polymer. - where component B corresponds to the free volume. - where component C corresponds to the volume resulting from the presence of binders, additives and other functional and non-functional ingredients. - Average particle size A mean Of the volume percent containing component A that can be assigned a mean value of A, the percentage identified as A1 of the total population is 1,mean A mean The particles are characterized as having a particle size distribution that can be greater than 0.1. - Average particle size A meanOf the volume percent containing component A that can be assigned the mean value A, the percentage identified as A2 of the total population 2,mean A mean The particles are characterized as having a particle size distribution that may be less than - Average volume percent of component A 1,mean >A mean The particles belonging to the population having a particle size distribution described by A form <100%, <95%, <85% or <80%, and the remainder of the component A, identified by A2, is located in the interstices between the larger particles. 2,mean mean Belongs to the group.

[0195] Considering the above design criteria, the following defines the order in which the components of the separator coated on the cathode layer can be combined to form a mixture of components A, B and C by a mixing process. - A portion of component A1 can be mixed with a portion of component C to provide a dispersed population of A1 particles. - A further portion of component A1 can be mixed with a portion of component A2 and component C to provide a dispersed population of A1 particles. - The remaining portions of component A2 and component C can be added stepwise to the mixture until the mixture contains the entirety of components A1, A2, B and C.

[0196] To facilitate the intended distribution of the above components, the following criteria can be applied to guide optimization of the component particle size distribution. The minimum characteristic particle size of the solid polymer electrolyte may be <1 micron, <0.5 micron or <0.2 micron. The maximum characteristic particle size of the solid polymer electrolyte may be >1.5 microns, <2.0 microns or <2.5 microns. The particle size distribution of the subpopulations can be approximated using a log-normal distribution function that includes individual or multiple components. Component A can be approximated using multiple components (A1 and A2) that have a log-normal distribution. ​

number

[0197] Separator layer coating process In one example, the separator can be coated, cast, deposited or placed on the positive electrode, the negative electrode or both electrodes to ensure high conformity between the separator layer and the electrodes. The coating process can be carried out according to the following configuration. i. The same separator formulation coated on the anode and cathode ii. Two different separator formulations coated onto the anode, allowing for optimized chemical and electrochemical stability between each electrode and the separator. iii. Successive layers of different formulations coated on the anode and / or cathode allowing for a gradient in separator composition that improves the chemical and electrochemical stability of the electrodes.

[0198] To ensure that the separator layer continuously covers the electrode it is covering, the width of the two covering layers can be the same, and the width of the separator layer can also be slightly larger than the covering width of the supporting electrode.

[0199] The separator layer slurry can be coated at a speed of 1-10 m / min using one of the coating methods described herein above (e.g., exemplary procedures 21, 22, 23 or 24). Following coating, the electrode roll passes through a set of four ovens where the temperature and fan ventilation can be set as follows: i. Oven 1 at 40-100℃ and 300-900 rpm ii. Oven 2 at 50-110°C and 300-900 rpm iii. Oven 3 at 60-120℃ and 300-900 rpm iv. Oven 4 at 80-140℃ and 300-900 rpm

[0200] Characterization of the polymer electrolyte 2D distribution in the separator layer The 2D distribution of component B is quantified from SEM-EDS images. In the SEM image 1900 as shown by Figure 19, the surface of the separator coating is shown with component B highlighted in white and the background in black. -Using nearest neighbor distance (NND) analysis, the 2D distribution of the polymer electrolytes can be clustered with an average NND of 2-5 μm. The maximum Feret distance, i.e. the longest distance between two points on the boundary of a polymer electrolyte particle, can be between 1 and 30 μm. - Particle area: 0.5~180μm 2 It can be said that: The circularity of the particles in the separator defined by the following may be between 0.2 and 1.0:

number

[0201] Tab Protection Strip In addition to the introduction of layers between the electrode, separator and current collector layers, the combination of the components described above can be facilitated through the placement of additional layers that can be placed to cover one or some portion of the previously existing layers. As an example, a tab protection layer can be introduced to protect the tabs extending from the current collector from shorting in the assembled form of the cell. The tab protection layer of the cell can include multiple materials, which can be characterized as powders insofar as they contain a large number of particles of similar composition and properties in an isolated population. These powders can be combined with other materials to form a slurry to facilitate the deposition of a continuous layer on a substrate that retains the functionality obtained from the composite. In the case of the present invention, this can be an assembly including a current collector or a previously manufactured electrode, a separator, or a combination thereof. In the following, a description of the component materials, the means by which the materials can be combined to form a slurry, the properties of the slurry, and a method for casting the slurry are provided.

[0202] The interfacial cathode-separator layer, and the composite containing the slurry from which the interfacial cathode-separator layer is obtained, can be formed from a combination of several materials with both active and passive functionality. Some of these candidate materials can be developed on a sacrificial basis during the formation of the slurry and later removed after casting of the slurry during the steps required to finalize the fabrication of said layer.

[0203] An additional coating adjacent to the electrode coating may be necessary to protect the tab from shorting due to contact with bare current collectors exposed on the edges of the electrodes.

[0204] A composite can be defined according to the following: where component A corresponds to the electrode active material (not present). where component B corresponds to the ion-conducting solid-state polymer (not present). - where the component C corresponds to the free volume. - where component D corresponds to binders, additives and other functional and non-functional ingredients. Thereby, the tab protection strip slurry may include the following ingredients: Ingredient A (Non-existent) Component B (Non-existent) Component C Component D - component D1: a binder comprising at least one compound selected from the group comprising polyethers, polyesters, carboxymethylcellulose or polymers based on at least one monomer such as methyl methacrylate, acrylonitrile, styrene, butadiene, acrylic acid or vinylidene fluoride; - Component D3: one or more surfactants for slurry homogeneity, such as sulfates, sulfonates, phosphates, carboxylates, etc. - Component D4: Dispersion solvents such as acetone, isopropanol, methanol, toluene, n-methylpyrrolidone and water - Component D6: one or more additives for mechanical integrity such as B2O3, Al2O3, γ-AlO(OH), Ga2O3, Y2O3, La2O3, etc., with a primary particle size of less than 1 μm.

[0205] Except for the solvent, the tab protectant slurry will contain the ingredients listed above in the following ranges: - Component D1 content of 5~100wt.% - Component D6 content of 0~95wt.% - Component D3 content of 0~2wt.%

[0206] Prior to coating, the tab protection slurry can be characterized by the following: - Viscosity of 500-3000cps at 85Hz - 3-40% solids content - Hegman gauge <30μm or <10μm - Particle size distribution such as: d10<1μm, d50<5μm, d90<10μm, d99<30μm

[0207] The thickness of the tab protection strip after calendering can be 5-40 μm with a width of 3-10 mm. Calendering can be carried out at room temperature (20° C.) to 140° C. in a low humidity environment.

[0208] Tab protection slurry mixing process The binder can be dissolved in the solvent at a concentration of 1-15 wt.%. After dissolution of the binder, the surfactant can be added to the solution and mixed for 30-90 minutes. The additives can then be added and mixed for 30-90 minutes. A sonication or homogenization step may be required to stabilize the suspension.

[0209] Alternatively, the above suspensions can be prepared by adding the additives first, then the surfactant, and finally the binder, the suspension properties remaining the same as those listed above.

[0210] Tab protection strip coating process The tab protection strip can be coated on the positive tab, the negative tab, or both electrode tabs. The tab protection strip is coated adjacent to the electrode coating to minimize overlap with the electrode coating and the presence of exposed current collectors between the electrode coating and the tab protection strip coating.

[0211] The tab protection slurry can be coated at a speed of 1-10 m / min using one of the coating methods described herein above. Following coating, the electrode roll passes through a set of ovens where drying conditions can be set to achieve an evaporation rate range of 0.1-15 g / min. Values ​​in this range can be optimized for reduced migration or spatial gradients of component D1 (binder), net-like distribution of component B (solid ionically conductive polymeric material), optimized uniformity of coating weight across the width of the coating, and good coating adhesion (≧10 gf / in). The latter parameter can be important to allow subsequent stamping of the electrode without compromising the integrity of the coating due to delamination on the surface or along the edges of the stamped electrode.

[0212] The methods described herein improve the manufacturing of rechargeable lithium-ion batteries, providing a method for replacing the liquid electrolyte component in conventional batteries with a solid-state electrolyte. These methods provide improved safety by reducing or eliminating the amount of liquid electrolyte in the finished cell, but also provide performance benefits for the resulting device. In this regard, the methods increase performance benefits by optimizing the energy and power density of the cell through an optimized powder pack strategy that results in increased specific capacity, reduced porosity, and reduced internal resistance.

[0213] The methods described herein, including the stepwise introduction of component materials tailored to provide a match between the material subsystems and free volume that fill the matrix, provide functionality for the components from which they are made. Additionally, the methods of material selection and deployment that support the slurry formulation and casting process increase the integrity and functionality of the individual and combined layers in the composite form. Not only does the order in which materials may be added affect the relative distribution of the component materials, but the method used to mix these materials when placed in contact for the intended intermixing effect also affects the overall distribution of the component materials.

[0214] Following mixing of the slurry, further complexities may be encountered during the casting procedure as the fluid dynamics of the cast slurry evolve towards those of a solid film. The properties of the solid film may be sensitive to parameters that define the pathway between the liquid and solid states. The described methods for bonding device layers during casting of the liquid phase slurry and bonding of the solid phase layer structure improve stability without compromising the functionality of the individual materials and the composite structures produced from the individual materials.

[0215] The described mixing and casting methods are provided herein for the production of slurries for the production of solid-state battery slurries and for the production of layers from the slurries, which when combined with other operations can produce an entire solid-state battery. The following methods are provided for producing a functioning cell or battery. Step 1. Process the ingredient powders (Components A, B, D1, D2, D5, D6, D7, D8) using various means such as mechanical processing and sieving to create a mass of said powders for the production of a slurry. a. Examples of materials subject to particle size engineering include, in a non-limiting manner, cathode or anode active materials, polymeric solid state electrolytes, inorganic solid electrolyte materials, inorganic mechanically stabilized powders, conductive additives, binder materials, salts, among others. Step 2. Evaluate the particle size distribution of the materials listed above using, for example, a combination of laser or white light particle size analysis, scanning electron microscopy, and test sieves. Step 3. Disperse the ingredients using a combination of high and low shear mixing techniques by stepwise combining the ingredients with each other and with the slurry vehicle. Non-limiting examples of the slurry vehicle can include the following (ingredients D1, D3, D4): Solvents, binders, surfactants, defoamers, thickeners, diluents, among others. Step 4. The slurry can be characterized by a stepwise parallel workflow using techniques such as rheometry, particle size analysis, Hegman gauge, among others. Step 5. The cathode slurry (components A, B, C, D1-D8) can be cast using roll-to-roll coating techniques such as slot die coating onto one or both sides of a current collector to form the cathode layer. a. The cathode layer may undergo in-line drying following the casting process. Step 6. The anode slurry (components A, B, C, D1-D8) can be cast using roll-to-roll coating techniques such as slot die coating onto one or both sides of a current collector to form the anode layer. a. The anode layer may undergo in-line drying following the casting process. Step 7. The anode or cathode structure can be subjected to a calendering process. Step 8. The separator slurry (components B, C, D1, D3, D4, D5, D6, D7, D8) can be cast using roll-to-roll coating techniques such as slot die coating onto one or both sides of the cathode or anode. a. The layered electrode-separator structure can undergo in-line drying following the casting process. Step 9. The layered electrode-separator structure can be subjected to a calendering process. Step 10. The layered electrode-separator structure may be subjected to a bake-out routine involving elevated temperature and / or reduced pressure. Step 11. The electrodes can then be interposed with one another such that the cathode and anode current collector tabs are aligned with the cathode and anode current collector tabs of the other electrode to form a stack. Step 12. The stacked electrodes can then be packaged in a sealed container, such as a pouch. Step 13. The cell may then undergo a configuration routine to prepare the cell for service.

[0216] In this manner, a slurry for applying a coating to an electrode structure for a solid-state battery cell can be formed utilizing optimized particle distribution and selectively staged component introduction. A technical effect of forming the slurry in this manner is that the coating formed therefrom can have reduced porosity and improved percolation networks. Additionally, the slurry can form a separator coating that includes a solid ionically conductive polymer material. A technical effect of incorporating the solid ionically conductive polymer material is to reduce resistance to Li-ion transport and provide mechanical stability in the formed battery cell.

[0217] In one example, the method includes dividing a solvent into a plurality of portions and, following a step sequence, mixing a solid ionically conductive polymer material, for example formed from polyphenylene sulfide or a liquid crystal polymer, in a first portion of the solvent to form a suspension, the solid ionically conductive polymer material having a molecular weight of 1×10 at room temperature. -5The method includes mixing a first additive in the suspension, and subsequent to mixing the first additive in the suspension, mixing a second portion of the solvent with the suspension to form a slurry having a solids content of 25-80 wt.%, a d50 particle size of less than 30 μm, a Hegman Gauge of less than 90 μm, and a viscosity of 500-2800 cps at 85 Hz, wherein the mixing includes mixing at high shear and mixing at low shear, and the low shear is between 10-55 rpm. A first example of the method further includes the high shear is between 0-1500 rpm. A second example of the method optionally including the first example of the method further includes the high shear is between 0-3500 rpm and the low shear is between 10-40 rpm. A third example of the method, optionally including one or more of the first and second examples of the method, further includes the high shear force being 0-1300 rpm and the low shear force being 10-45 rpm. A fourth example of the method, optionally including one or more of the first to third examples of the method, further includes the mixing includes simultaneously mixing at high shear and mixing at low shear. A fifth example of the method, optionally including one or more of the first to fourth examples of the method, further includes the amount of the first portion of the solvent and the amount of the second portion of the solvent are approximately equal. A sixth example of the method, optionally including one or more of the first to fifth examples of the method, further includes the first additive includes an electrode active material, a binder, a surfactant, or an inorganic ceramic. A seventh example of the method, optionally including one or more of the first to sixth examples of the method, further includes the mixing of the first additive in the suspension includes mixing the first additive and one or more additional additives in the suspension.An eighth example of the method, optionally including one or more of the first through seventh examples of the method, further includes: the first additive is an inorganic ceramic; and the one or more further additives are a binder and a surfactant; and mixing the first additive and the one or more further additives in the suspension further includes mixing the binder and surfactant in a third portion of the solvent to form a solution, mixing the inorganic ceramic in the solution, following mixing the inorganic ceramic in the solution, dividing the solution into multiple portions, mixing a portion of the solution in the suspension, and then mixing the remaining portion of the solution in the suspension. A ninth example of the method, optionally including one or more of the first through eighth examples of the method, further includes the first additive being an electrode active material, and mixing the solid ionically conductive polymer material in the first portion of the solvent to form the suspension includes dividing the binder into a plurality of portions, mixing the first portion of the binder in the first portion of the solvent to form a first solution, dividing the first solution into a plurality of portions, mixing an electronic conductor in the first portion of the first solution to form the suspension, and mixing the solid ionically conductive polymer material and a second portion of the first solution in the suspension, and mixing the first additive in the suspension includes mixing the electrode active material and the remaining portion of the first solution in the suspension. A tenth example of the method, optionally including one or more of the first through ninth examples of the method, further includes the electrode active material being a cathode active material. An eleventh example of the method, optionally including one or more of the first through tenth examples of the method, further includes mixing the electrode active material and a remaining portion of the first solution in the suspension includes dividing the first additive into multiple portions, mixing the first portion of the electrode active material and the third portion of the first solution with the suspension for 45-120 minutes, and then mixing the second portion of the electrode active material and the fourth portion of the first solution with the suspension for 2-16 hours. A twelfth example of the method, optionally including one or more of the first through eleventh examples of the method, further includes the viscosity being 2000-2600 cps at 85 Hz.A thirteenth example of the method, optionally including one or more of the first through twelfth examples of the method, further includes that the electrode active material is an anode active material. A fourteenth example of the method, optionally including one or more of the first through thirteenth examples of the method, further includes, following mixing the electrode active material and the remaining portion of the first solution in the suspension, mixing a second portion of the binder with a third portion of the solvent to form a second solution, and mixing the second solution in the suspension. A fifteenth example of the method, optionally including one or more of the first through fourteenth examples of the method, further includes that the solids content is 25-75 wt.%. A sixteenth example of the method, optionally including one or more of the first through fifteenth examples of the method, further includes that the viscosity is 1100-2800 cps at 85 Hz. A seventeenth example of the method, optionally including one or more of the first through sixteenth examples of the method, further includes mixing the electrode active material and the remaining portion of the first solution in the suspension includes dividing the electrode active material into a plurality of portions, mixing a first portion of the electrode active material and a third portion of the first solution with the suspension for 45-120 minutes, then mixing a second portion of the electrode active material and a fourth portion of the first solution with the suspension for 2-16 hours, then mixing a fifth portion of the first solution with the suspension for 30-90 minutes. An eighteenth example of the method, optionally including one or more of the first through seventeenth examples of the method, further includes a solids content of 25-65 wt.%. A nineteenth example of the method, optionally including one or more of the first through eighteenth examples of the method, further includes a viscosity of 500-2600 cps at 85 Hz. A twentieth example of the method, optionally including one or more of the first through nineteenth examples of the method, further includes the slurry having a d10 particle size of less than 1 μm, a d90 particle size of less than 60 μm, and a d99 particle size of less than 140 μm. A twenty-first example of the method, optionally including one or more of the first through twentieth examples of the method, further includes the slurry having a d99 particle size of less than 100 μm. A twenty-second example of the method, optionally including one or more of the first through twenty-first examples of the method, further includes the Hegman Gauge being less than 80 μm.A 23rd example of a method optionally including one or more of the 1st to 22nd examples of the method further includes that the Hegman gauge is less than 50 μm. A 24th example of a method optionally including one or more of the 1st to 23rd examples of the method further includes that mixing the second portion of the solvent with the suspension to form a slurry is performed under vacuum.

[0218] In another example, a method for forming a coating on an electrode structure includes dividing a solvent into a plurality of portions and, according to a step sequence, mixing a solid ion-conductive polymer material formed from, for example, polyphenylene sulfide or a liquid crystal polymer in the first portion of the solvent to form a suspension, wherein the solid ion-conductive polymer material has an ionic conductivity exceeding 1×10 -5 S / cm at room temperature, the solid ion-conductive polymer material is in a glassy state at room temperature, the first portion of the solvent is approximately half of the total solvent content, mixing a first additive in the suspension, subsequent to mixing the first additive in the suspension, mixing the second portion of the solvent with the suspension to form a slurry having a solid content of 25 to 80 wt.%, a d50 particle size of less than 30 μm, a Hegman gauge of less than 90 μm, and a viscosity of 500 to 2800 cps at 85 Hz, wherein the mixing includes mixing at a high shear force and mixing at a low shear force, the low shear force being 10 to 55 rpm, coating the slurry on the electrode structure, drying the coated electrode structure, and calendaring the coated electrode structure, the electrode structure including one of an anode material coating deposited on an anode current collector and a cathode material coating deposited on a cathode current collector, and the adhesion interface between the coating and the electrode structure having a 180° peel strength exceeding 200 gf / in.

[0219] In yet another example, a method includes dividing a solvent into a plurality of portions and dispersing a solid ionically conductive polymer material, for example formed from polyphenylene sulfide or a liquid crystal polymer, in a first portion of the solvent under low shear to form a suspension, the solid ionically conductive polymer material having a molecular weight of about 1×10 at room temperature. -5The method includes mixing a binder in the suspension and, following mixing the binder in the suspension, mixing a second portion of a solvent with the suspension to form a slurry having a solids content of 25-55 wt.%, a d50 particle size of less than 15 μm, a Hegman Gauge of less than 90 μm, and a viscosity of 500-2200 cps at 85 Hz, wherein the mixing includes mixing at high shear and mixing at low shear, wherein the low shear is 10-55 rpm. The first example of the method further includes the high shear is 0-1500 rpm. A second example of the method optionally including the first example of the method further includes the high shear is 0-3500 rpm and the low shear is 10-40 rpm. A third example of the method, optionally including one or more of the first and second examples of the method, further includes that the high shear force is 0-1300 rpm and the low shear force is 10-45 rpm. A fourth example of the method, optionally including one or more of the first through third examples of the method, further includes that the low shear force is about 15 rpm. A fifth example of the method, optionally including one or more of the first through fourth examples of the method, further includes that the mixing comprises simultaneously mixing at high shear force and mixing at low shear force. A sixth example of the method, optionally including one or more of the first through fifth examples of the method, further includes that the amount of the first portion of the solvent is about 15% of the total amount of the solvent. A seventh example of the method, optionally including one or more of the first through sixth examples of the method, further includes that mixing the binder in the suspension comprises mixing the binder and one or more additives in the suspension. An eighth example of the method, optionally including one or more of the first through seventh examples of the method, further includes the one or more additives including an inorganic ceramic, and mixing the binder and the one or more additives in the suspension includes mixing the inorganic ceramic in a third portion of the solvent to form a solution, dividing the solution into multiple portions, mixing a portion of the solution in the suspension, and then mixing the remaining portion of the solution in the suspension.A ninth example of the method, optionally including one or more of the first through eighth examples of the method, further includes the one or more additives further comprising a surfactant, and mixing the binder and one or more additives in the suspension further comprises first mixing the binder and the surfactant in a third portion of the solvent. A tenth example of the method, optionally including one or more of the first through ninth examples of the method, further comprises dividing the inorganic ceramic into a plurality of portions and mixing the first portion of the inorganic ceramic in the first portion of the solvent before dispersing the solid ionically conductive polymer material in the first portion of the solvent to form a suspension. An eleventh example of the method, optionally including one or more of the first through tenth examples of the method, further includes the one or more additives further comprising a second portion of the inorganic ceramic, and mixing the binder and one or more additives in the suspension further comprises mixing the binder in the suspension, mixing the second portion of the inorganic ceramic in the third portion of the solvent to form a solution, and mixing the binder in the suspension followed by mixing the solution in the suspension. A twelfth example of the method, optionally including one or more of the first through eleventh examples of the method, further includes mixing the solution in the suspension includes dividing the solution into a plurality of portions, mixing a portion of the solution in the suspension, and then mixing the remaining portion of the solution in the suspension. A thirteenth example of the method, optionally including one or more of the first through twelfth examples of the method, further includes the slurry having a d10 particle size of less than 1 μm, a d90 particle size of less than 60 μm, and a d99 particle size of less than 100 μm. A fourteenth example of the method, optionally including one or more of the first through thirteenth examples of the method, further includes a Hegman Gauge of less than 50 μm. A fifteenth example of the method, optionally including one or more of the first through fourteenth examples of the method, further includes mixing a second portion of the solvent with the suspension to form a slurry is performed under vacuum.

[0220] In another example, the slurry for forming the coating on the electrode structure is a solid, ionically conductive polymer material, for example made from polyphenylene sulfide or liquid crystal polymer, having a concentration of 1×10 at room temperature. -5 % d50 particle size less than 30 μm, Hegman Gauge less than 90 μm, and a viscosity of 500-2800 cps at 85 Hz; the slurry being formed from a process of sequentially mixing the solid ionically conductive polymer material, the solvent, and the one or more additives, the process including dividing the solvent into a plurality of portions, mixing the solid ionically conductive polymer material in a first portion of the solvent to form a suspension, the first portion of the solvent being approximately half of the total solvent content, mixing the one or more additives in the suspension, and subsequent to mixing the one or more additives in the suspension, mixing a second portion of the solvent with the suspension to form the slurry; the mixing including mixing at high shear and mixing at low shear, the low shear being between 10-55 rpm. The first example of the slurry further includes that the slurry has a d10 particle size of less than 1 μm, a d90 particle size of less than 60 μm, and a d99 particle size of less than 140 μm.

[0221] In yet another example, a coated hybrid electrode includes an anode current collector, a cathode current collector, an anode material coating, a cathode material coating, and a solid polymer electrolyte coating formed as a separator, the anode material coating, the cathode material coating, and the solid polymer electrolyte coating are formed from a first slurry, a second slurry, and a third slurry, respectively, each of the first slurry, the second slurry, and the third slurry are formed by dividing a solvent into a plurality of portions and mixing a solid ionically conductive polymer material, for example, formed from polyphenylene sulfide or a liquid crystal polymer, in the first portion of the solvent to form a suspension, the solid ionically conductive polymer material having a molecular weight of 1×10 at room temperature. -5The solid ionically conductive polymeric material has an ionic conductivity of greater than 1.0 S / cm, and is in a glassy state at room temperature; mixing the additive in the suspension; and subsequent to mixing the additive in the suspension, mixing a second portion of the solvent with the suspension to form a composition having a solids content of 25-80 wt.%, a d50 particle size of less than 30 μm, a Hegman Gauge of less than 90 μm, and a viscosity of 500-2800 cps at 85 Hz, where the mixing includes mixing at high shear and mixing at low shear, where the low shear is 10-55 rpm. The first example of the coated hybrid electrode further includes that the mixing includes simultaneously mixing at high shear and mixing at low shear. A second example of the coated hybrid electrode optionally including the first example of the coated hybrid electrode further includes that the Hegman Gauge of the first slurry is less than 50 μm and the viscosity of the first slurry is 2000-2600 cps at 85 Hz. A third example of a coated hybrid electrode optionally comprising one or more of the first and second examples of the coated hybrid electrode further comprises a solids content of the second slurry being 25-65 wt.%, a Hegman gauge of the second slurry being less than 80 μm, and a viscosity of the second slurry being 1100-2800 cps at 85 Hz. A fourth example of a coated hybrid electrode optionally comprising one or more of the first through third examples of the coated hybrid electrode further comprises a solids content of the third slurry being 25-55 wt.%, a d50 particle size of the third slurry being less than 15 μm, and a viscosity of the third slurry being 500-2200 cps at 85 Hz. A fifth example of a coated hybrid electrode, optionally including one or more of the first through fourth examples of the coated hybrid electrode, further includes a solid polymer electrolyte coating dispersed between the anode material coating and the cathode material coating, and the solid polymer electrolyte coating having a different composition in a first region adjacent the cathode material coating than a second region adjacent the anode material coating.A sixth example of the coated hybrid electrode, optionally comprising one or more of the first through fifth examples of the coated hybrid electrode, further comprises a cathode-separator interfacial coating disposed between the cathode material coating and the solid polymer electrolyte coating, the cathode-separator interfacial coating comprising a solid ionically conductive polymer material, the cathode-separator interfacial coating being formed from a fourth slurry, the fourth slurry having a solids content of 25-80 wt.%, a d50 particle size of less than 30 μm, a Hegman Gauge of less than 50 μm, and a viscosity of 2000-2600 cps at 85 Hz. A seventh example of a coated hybrid electrode, optionally comprising one or more of the first through sixth examples of the coated hybrid electrode, further comprises an anode-separator interfacial coating disposed between the anode material coating and the solid polymer electrolyte coating, the anode-separator interfacial coating comprising a solid ionically conductive polymer material, the anode-separator interfacial coating being formed from a fifth slurry, the fifth slurry having a solids content of 25-75 wt.%, a d50 particle size of less than 30 μm, a Hegman Gauge of less than 90 μm, and a viscosity of 500-2600 cps at 85 Hz. An eighth example of a coated hybrid electrode, optionally including one or more of the first through seventh examples of the coated hybrid electrode, further comprises a first tab protective strip disposed between the anode current collector and the anode material coating and a second tab protective strip disposed between the cathode current collector and the cathode material coating, the first tab protective strip and the second tab protective strip being formed from a sixth slurry and a seventh slurry, respectively, each of the sixth slurry and the seventh slurry having a solids content of 3-40 wt.%, a d50 particle size of less than 5 μm, a Hegman Gauge of less than 30 μm, and a viscosity of 500-3000 cps at 85 Hz.

[0222] In yet another example, a battery cell includes a plurality of hybrid electrodes, each of the plurality of hybrid electrodes including an anode current collector, a cathode current collector, an anode material coating, a cathode material coating, and a solid polymer electrolyte coating formed as a separator; and a sealed pouch containing the plurality of hybrid electrodes, the anode material coating, the cathode material coating, and the solid polymer electrolyte coating are each formed from a plurality of slurries, each of the plurality of slurries being formed according to a step sequence of dividing a solvent into a plurality of portions and mixing a solid ionically conductive polymer material, for example formed from polyphenylene sulfide or a liquid crystal polymer, in at least a first portion of the solvent to form a suspension, the solid ionically conductive polymer material having a molecular weight of about 1×10 at room temperature. -5 The solid ionically conductive polymeric material has an ionic conductivity of greater than 100 S / cm, the solid ionically conductive polymeric material being in a glassy state at room temperature; mixing the additive in the suspension; and subsequent to mixing the additive in the suspension, mixing a second portion of the solvent with the suspension to form a composition having a solids content of 25-80 wt.%, a d50 particle size of less than 30 μm, a Hegman Gauge of less than 90 μm, and a viscosity of 500-2800 cps at 85 Hz, the mixing including mixing at high shear and mixing at low shear, the low shear being between 10-55 rpm. The first example of the battery cell further includes that the mixing includes simultaneously mixing at high shear and mixing at low shear. A second example of the battery cell optionally including the first example of the battery cell further includes that each of the plurality of hybrid electrodes further comprises a first tab protection strip disposed on the anode current collector and a second tab protection strip disposed on the cathode current collector.

[0223] The following claims particularly recite certain combinations and subcombinations that are deemed novel and unobvious. The claims may recite a "an" element or a "first" element or equivalents. Such claims should be understood to include the incorporation of one or more such elements without requiring or excluding two or more such elements. Other combinations and subcombinations of the disclosed features, functions, elements and / or properties may be claimed by amending the claims or presenting new claims in this or a related application. Such claims, whether broader, narrower, equal or different in scope than the original claims, are similarly deemed to be within the subject matter of this disclosure.

Claims

1. dividing the solvent into a first portion and a second portion; 1×10 at room temperature -5 dispersing a solid, ionically conductive polymeric material having an ionic conductivity of greater than 1.0 S / cm and in a glassy state at room temperature in a first portion of said solvent under low shear to form a first suspension; mixing a binder in the first suspension; and Subsequent to mixing the binder in the first suspension, mixing a second portion of the solvent with the first suspension to form a slurry having a solids content of 25-55 wt.%; Including, wherein the slurry has, in any part, a d50 particle size of less than 15 μm, a Hegman Gauge of less than 90 μm, and a viscosity of 500-2200 cps at 85 Hz; 20. The method of claim 19, wherein mixing a binder in the first suspension and mixing a second portion of the solvent with the first suspension comprises one or both of high shear mixing and low shear mixing using a multi-shaft mixer equipped with a low shear anchor agitator or a low shear helical paddle and a high shear disperser, and the low shear mixing speed is between 10 and 55 rpm.

2. 2. The method of claim 1, wherein the slurry forms a separator layer of a battery cell, and further comprising calendering the slurry onto a cathode layer of the battery cell, the separator layer having a thickness of 5 to 50 μm after calendering.

3. 3. The method of claim 1 or 2, wherein the amount of the first portion of the solvent is 15% of the total amount of the solvent.

4. The method of any one of claims 1 to 3, further comprising mixing the slurry under vacuum.

5. mixing the binder in the first suspension; and subsequent to mixing the binder in the first suspension, mixing a second portion of the solvent with the first suspension to form a slurry having a solids content of 25-55 wt. further dividing the second portion of the solvent into a third portion and a remaining portion of the second portion; mixing the binder, a third portion of the solvent, and one or more further additives under high shear to form a second suspension; mixing the second suspension in the first suspension; and mixing the remaining portion of the second portion of the solvent with the resulting suspension to form a slurry having a solids content of 25-55 wt.%; The method according to any one of claims 1 to 4, comprising:

6. The method of claim 5 , wherein the one or more further additives are surfactants.

7. 7. The method of claim 5 or 6, wherein mixing the second suspension in the first suspension comprises mixing the second suspension in portions with the first suspension.

8. 8. The method of any one of claims 1 to 7, wherein the slurry has in any part a d10 particle size of less than 1 μm, a d90 particle size of less than 60 μm, and a d99 particle size of less than 100 μm.

9. 1. A method for forming a coating on an electrode structure, comprising: dividing the solvent into a first portion and a second portion; Following the step sequence, 1×10 -5 mixing a solid, ionically conductive polymer material having an ionic conductivity of greater than 100 S / cm in a first portion of the solvent to form a suspension, wherein the solid, ionically conductive polymer material is in a glassy state at room temperature and the first portion of the solvent is approximately half of the total solvent content; mixing a first additive in said suspension; Subsequent to mixing the first additive in the suspension, mixing a second portion of the solvent with the suspension to form a slurry having a solids content of 25-80 wt.%, wherein the slurry has, in any portion, a d50 particle size of less than 30 μm, a Hegman Gauge of less than 90 μm, and a viscosity of 500-2800 cps at 85 Hz; said mixing comprising one or both of high shear mixing and low shear mixing using a multi-shaft mixer equipped with a low shear anchor agitator or a low shear helical paddle and a high shear disperser, said low shear mixing speed being between 10 and 55 rpm; coating the slurry onto the electrode structure; drying the coated electrode structure; and calendering the coated electrode structure; Including, the electrode structure includes one of an anode material coating deposited on an anode current collector and a cathode material coating deposited on a cathode current collector; The method of claim 1, wherein the adhesive interface between the coating and the electrode structure has a 180° peel strength of greater than 200 gf / in.

10. 10. The method of claim 9, further comprising affecting the viscosity, d50 particle size and Hegman gauge of the slurry by said mixing.

11. The method of claim 9 or 10, wherein the coating comprises one or more of roll-to-roll coating and slot-die coating.

12. The method of any one of claims 9 to 11, further comprising mixing the slurry under vacuum before said coating.

13. A method according to any one of claims 9 to 12, wherein the coating conforms to and penetrates the surface of the electrode structure.

14. A plurality of hybrid electrodes, each of the plurality of hybrid electrodes comprising: an anode current collector, a cathode current collector; Anode material coating, a cathode material coating; and A solid polymer electrolyte coating formed as a separator a plurality of hybrid electrodes comprising: a sealed pouch containing the plurality of hybrid electrodes; and Equipped with The anode material coating, the cathode material coating, and the solid polymer electrolyte coating are each formed from a plurality of slurries, each of the plurality of slurries comprising: dividing the solvent into a first portion and a second portion; Following the step sequence, 1×10 -5 mixing a solid, ionically conductive polymeric material having an ionic conductivity of greater than 1.5 S / cm and in a glassy state at room temperature in at least a first portion of said solvent to form a suspension; mixing an additive in said suspension; and Subsequent to said mixing of said additive in said suspension, mixing a second portion of said solvent with said suspension to form a composition having a solids content of 25-80 wt.%, wherein said composition has, in any portion, a d50 particle size of less than 30 μm, a Hegman Gauge of less than 90 μm, and a viscosity of 500-2800 cps at 85 Hz; is formed by The mixing includes one or both of high shear mixing and low shear mixing using a multi-shaft mixer equipped with a low shear anchor agitator or a low shear helical paddle and a high shear disperser, and the low shear mixing speed is 10 to 55 rpm.

15. 15. The battery cell of claim 14, wherein the plurality of slurries are further formed by differentially adjusting d50 particle size, Hegman gauge, viscosity, and relative proportions of solid, ionically conductive polymer material and additives in electrode layers and solid electrolyte layers, the relative proportions including relative volume percentages of the solid, ionically conductive polymer material and relative volume percentages of the additives.

16. 16. The battery cell of claim 14 or 15, wherein at least one of the slurries forming the anode material coating has a solids content of 40-65 wt. %, and further has a Hegman gauge of less than 80 μm anywhere in the range, and a viscosity of 1100-2800 cps at 85 Hz.

17. 17. The battery cell of any one of claims 14 to 16, wherein at least one of the plurality of slurries forming the solid polymer electrolyte coating has a solids content of 40 to 55 wt.%, and further has, at any portion, a d50 particle size of less than 15 μm, a Hegman Gauge of less than 50 μm, and a viscosity of 2000 to 4500 cps at 85 Hz.

18. 18. The battery cell of any one of claims 14 to 17, wherein at least one of the slurries forming the cathode material coating has a solids content of 45 to 75 wt.%, and further has a Hegman gauge of less than 80 μm anywhere in the range, and a viscosity of 1000 to 2600 cps at 85 Hz.

19. 19. The battery cell of any one of claims 14 to 18, wherein the solid, ionically conductive polymer material is formed from particles and the solid polymer electrolyte coating comprises particles clustered with an average nearest neighbor distance of 2 μm to 5 μm.

20. 20. The battery cell of any one of claims 14 to 19, wherein the solid polymer electrolyte coating has a different composition in a first region adjacent the cathode material coating and a second region adjacent the anode material coating.

Citation Information

Patent Citations

  • Lithium secondary cell

    JP1999097025A

  • Ether compound electrolyte battery

    JP2001243987A

  • Lithium secondary battery and production process thereof

    JP2002329495A

  • Battery with inorganic / organic porous membrane

    JP2011518404A

  • Crosslinked polymer electrolyte and use thereof

    WO2004113443A1